Improved hydrophobic aerogel materials
By developing aerogel materials mainly based on silica, combined with hydrophobicity, silicon and high-temperature oxygen-reducing treatment technology, the problem of insufficient durability and treatmentability of existing aerogel materials in water environments has been solved, and good results have been achieved. Combustion and self-heating properties, suitable for a variety of applications.
Patent Information
- Application Number
- CN202210522793.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2015-09-25
- Filing Date
- 2015-10-02
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2035-10-02
AI Technical Summary
The existing low-density aerogel materials exhibit poor durability and handling in water environments, and their combustion and self-heating properties are insufficient, making it difficult to meet the needs of various applications.
Aerogel composition mainly composed of silica was developed, using hydrophobicity combined with silicon and high temperature reduction by providing low density, low thermal conductivity and low water absorption, with good combustion heat and high thermal decomposition temperatures. Oxygen treatment technology enhances the durability and handling of materials.
It has achieved aerogel materials with good performance in water environments, with good combustion and self-heating properties, and is suitable for a variety of applications, including insulation, sound insulation and energy storage.
Smart Images

Figure CN114804124B_ABST
Abstract
Description
[0001] The present invention is a divisional application of a PCT patent application entered into China with Chinese patent application number 201580053603.0, invention name “Improved Hydrophobic Aerogel Material” and international application date October 2, 2015.
[0002] CROSS REFERENCE TO RELATED APPLICATIONS
[0003] This application claims priority to U.S. Provisional Application No. 62 / 059,555, filed on October 3, 2014; U.S. Provisional Application No. 62 / 118,864, filed on February 20, 2015; and U.S. Provisional Application No. 62 / 232,945, filed on September 25, 2015; the contents of which are incorporated herein by reference, with the definitions of any terms in this application controlling. Background Art
[0004] Low-density aerogel materials are widely regarded as the best solid insulators available. Aerogels act as insulators primarily because they minimize conductivity (low structural density results in a circuitous path for energy transfer through the solid skeleton), convection (large pore volume and very small pore size result in minimal convection), and radiation (IR absorbing or scattering dopants can be easily dispersed throughout the aerogel matrix). Aerogels can be used in a wide range of applications, including: heating and cooling insulation, sound insulation, dielectrics, aviation, energy storage and production, and filtration. Furthermore, aerogel materials exhibit many other interesting acoustic, optical, mechanical, and chemical properties, making them useful in a wide variety of insulating and non-insulating applications. Summary of the invention
[0005] In a general aspect, the present invention can provide an aerogel composition that is durable and easy to handle, that has good performance in an aqueous environment, and that also has good combustion and self-heating properties. In certain embodiments, the present invention provides an aerogel composition that is a flexible, resilient, and self-supporting reinforced aerogel composition that has good performance in an aqueous environment, and that also has good combustion and self-heating properties.
[0006] In another general aspect, the present invention can provide an aerogel composition comprising a silica-based skeleton having the following properties: a) 0.60 g / cm 3 or less density; b) 50mW / m *K or less; and c) 40 wt% or less water absorption. In certain embodiments, the aerogel composition of the present invention has a heat of combustion of 717 cal / g or less. In certain embodiments, the aerogel composition of the present invention has a thermal decomposition temperature of a hydrophobic organic material between 300°C and 700°C. In certain embodiments, the aerogel composition of the present invention has a hydrophobic organic material having a thermal decomposition temperature of 0.50 g / cm 3 or less, 0.40g / cm 3 or less, 0.30g / cm 3 or less, 0.25g / cm 3 or less, or 0.20g / cm 3 In certain embodiments, the aerogel composition of the present invention has a density of 45 mW / M * K or less, 40mW / M * K or less, 35mW / M * K or less, 30mW / M * K or less, 25mW / M * K or less, 20mW / M * Thermal conductivity of 1000K or less, or 5mW / M * K to 50mW / M * K. In certain embodiments, the aerogel composition of the present invention has a water absorption of 35 wt% or less, 30 wt% or less, 25 wt% or less, 20 wt% or less, 15 wt% or less, or 10 wt% or less. In certain embodiments, the aerogel composition of the present invention has a heat of combustion of 650 cal / g or less, 600 cal / g or less, 550 cal / g or less, 500 cal / g or less, 450 cal / g or less, 400 cal / g or less, or a heat of combustion between 150 cal / g and 717 cal / g. In certain embodiments, the aerogel composition of the present invention has a thermal decomposition temperature start of a hydrophobic organic material of 400°C or more, 450°C or more, 475°C or more, 500°C or more, 525°C or more, 550°C or more, 575°C or more, 600°C or more, or a thermal decomposition temperature start of a hydrophobic organic material between 400°C and 700°C. In a preferred embodiment, the aerogel composition of the present invention has the following properties: a) 0.40 g / cm 3 or less density; b) 40mW / M *K or less; c) 40 wt% or less water absorption; and d) 140 cal / g to 600 cal / g of heat of combustion. In certain embodiments, the aerogel composition of the present invention has a thermal decomposition temperature of 525°C to 700°C. In certain embodiments, the aerogel composition of the present invention has a T between about 0.01 and 0.5. 1-2 :T 3 The ratio of silicon dioxide species and / or Q between about 0.1 and 1.5 2-3 :Q 4 In some embodiments, the aerogel composition of the present invention is a reinforced aerogel composition, a fiber reinforced aerogel composition, or an aerogel blanket composition. In some embodiments, the aerogel composition of the present invention has a hydrophobic organic content of about 1 wt % to about 30 wt %, about 1 wt % to about 25 wt %, about 1 wt % to about 20 wt %, about 1 wt % to about 15 wt %, about 1 wt % to about 10 wt %, or about 1 wt % to about 5 wt %.
[0007] In another general aspect, the present invention may provide a method for preparing an aerogel composition, comprising: a) providing a precursor solution comprising a silica gel precursor material, a solvent, and optionally a catalyst; b) converting the silica gel precursor material in the precursor solution into a gel material or composition; c) extracting at least a portion of the solvent from the gel material or composition to obtain an aerogel material or composition; d) incorporating at least one hydrophobic-binding silicon into the aerogel material or composition by one or both of: i) including at least one silica gel precursor material having at least one hydrophobic group in the precursor solution, or ii) exposing the precursor solution, gel composition, or aerogel composition to a hydrophobizing agent; and e) exposing the aerogel material or composition to a reduced oxygen atmosphere at a temperature greater than 300° C. In certain embodiments, the method of the present invention comprises exposing the aerogel composition to a reduced oxygen atmosphere at a temperature between 300° C. and 650° C. for about 30 seconds to about 200 minutes to obtain a treated aerogel material or composition. In certain embodiments, the method of the present invention includes incorporating a reinforcing material into an aerogel composition by combining the reinforcing material with the precursor solution before or during the conversion of the silica gel precursor material in the precursor solution into the gel composition. In a preferred embodiment, the reinforcing material comprises a continuous sheet of a fiber-reinforced material. In certain embodiments, the method of the present invention includes limiting the temperature exposure of the heat treatment of the aerogel composition to a temperature below 850°C. In certain embodiments, the method of the present invention converts at least one gel precursor in the precursor solution into a gel material for a total time of 30 hours or less. In certain embodiments, the method of the present invention includes a reduced oxygen atmosphere including 0.1 volume % to 5 volume % oxygen. In certain embodiments, the method of the present invention includes the step of incorporating at least one hydrophobic binding silicon into the aerogel material or composition to provide a hydrophobic organic content in the aerogel composition between about 1 wt % and about 25 wt %. In a preferred embodiment, the method of the present invention produces an aerogel composition. In certain embodiments, the aerogel material or composition produced by the method of the present invention has the following properties: a) 0.60 g / cm 3 or less density; b) 50mW / m * K or less; c) 40wt% or less water absorption; d) 150cal / g to 717cal / g heat of combustion; and e) 300°C to 700°C thermal decomposition temperature of the hydrophobic organic material.
[0008] In another general aspect, the present invention may provide a method of preparing an aerogel composition, comprising: a) making an aerogel composition comprising at least one hydrophobically bound silicon; and b) exposing the aerogel composition to a reduced oxygen atmosphere at a temperature greater than 300°C. In another general aspect, the present invention may provide a method of exposing a first aerogel composition comprising at least one hydrophobically bound silicon to a reduced oxygen atmosphere at a temperature greater than 300°C to obtain a second aerogel composition. In certain embodiments, the method of the present invention comprises exposing the aerogel composition to a reduced oxygen atmosphere at a temperature between 300°C and 650°C for a period of about 30 seconds to about 200 minutes to obtain a treated aerogel material or composition. In certain embodiments, the method of the present invention comprises thermal treatment of the aerogel material or composition with the temperature exposure limited to a temperature less than 850°C. In certain embodiments, the method of the present invention comprises a silica-based aerogel composition. In certain embodiments, the method of the present invention comprises the aerogel composition being a reinforced aerogel composition. In certain embodiments, the method of the present invention comprises the reduced oxygen atmosphere comprising 0.1 vol% to 5 vol% oxygen. In certain embodiments, the methods of the present invention include treating an aerogel composition having a hydrophobic organic content between about 1 wt% and about 25 wt%. In certain embodiments, the methods of the present invention produce a treated aerogel material or composition having improved hydrophobicity relative to the aerogel composition prior to the treatment method. In certain embodiments, the methods of the present invention produce a treated aerogel composition having a lower water absorption rate relative to the aerogel composition prior to the treatment method. In certain embodiments, the methods of the present invention produce a treated aerogel material or composition having a lower heat of combustion relative to the aerogel composition prior to the treatment method. In certain embodiments, the methods of the present invention produce a treated aerogel composition having a higher thermal decomposition temperature onset relative to the aerogel composition prior to the treatment method. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 An example of the aerogel composition of the present invention is 29 Si solid-state NMR spectrum.
[0010] Figure 2 The following is a TGA / DSC analysis chart of an example of the aerogel composition of the present invention. DETAILED DESCRIPTION
[0011] Aerogel is a porous material with openings, including a skeleton of interconnected structures, a corresponding network of pores integrated into the skeleton, and an interstitial phase within the network of pores that primarily includes a gas, such as air. Aerogels are characterized by low density, high porosity, large surface area, and small pore size. Aerogels are distinguished from other porous materials by their physical and structural properties.
[0012] As used herein, the term "aerogel" or "aerogel material" refers to a gel comprising an interconnected structural backbone, a corresponding network of interconnected pores integrated within the backbone, and containing a gas, such as air, as a dispersed interstitial medium; and characterized by the following physical and structural properties attributable to the aerogel (as determined by the nitrogen porosity test): (a) an average pore diameter of about 2 nm to about 100 nm, (b) a porosity of at least 80% or greater, and (c) a porosity of about 20 nm or greater. 2 / g or greater surface area.
[0013] The aerogel materials of the present invention therefore include any aerogel or other open-cell compound that meets the definition elements set forth in the preceding paragraph; including compounds that can be classified as xerogels, cryogels, ambient drying gels, microporous materials, and the like.
[0014] Aerogel materials may also be further characterized by other physical properties, including: (d) a pore volume of about 2.0 mL / g or greater, preferably about 3.0 mL / g or greater; (e) a density of about 0.50 g / cc or less, preferably about 0.25 g / cc or less; and (f) at least 50% of the pore volume comprises pores having pore diameters of 2 to 50 nm, although meeting these other properties is not a required characteristic of a compound to be an aerogel material.
[0015] In the context of the present invention, the term "innovative processing and extraction techniques" refers to methods of replacing the liquid interstitial phase in a wet gel material with a gas, such as air, in a manner that results in low pore collapse and low shrinkage of the gel's skeletal structure. Drying techniques, such as atmospheric evaporation, often introduce strong capillary pressures and other mass transfer restrictions at the liquid-gas interface of the interstitial phase being evaporated or removed. The strong capillary forces generated by liquid evaporation or removal can cause significant pore shrinkage and skeletal collapse within the gel material. The use of innovative processing and extraction techniques during liquid interstitial phase extraction reduces the negative effects of capillary forces on the pores and skeletal structure of the gel during liquid phase extraction.
[0016] In certain embodiments, the innovative processing and extraction techniques use near-critical or supercritical fluids, or near-critical or supercritical conditions, to extract the liquid interstitial phase from the wet gel material. This can be achieved by removing the liquid interstitial phase from the gel at a temperature close to or above the critical point of the liquid or liquid mixture. Near-critical or supercritical fluid extraction processes can be optimized using co-solvents and solvent exchange.
[0017] In certain embodiments, the novel processing and extraction techniques include modifying the gel skeleton to reduce the irreversible effects of capillary pressure and other mass transfer limitations at the liquid-air interface. This embodiment may include treating the gel skeleton with a hydrophobizing agent, or other functionalizing agent, which can allow the gel skeleton to withstand or recover from any collapse forces during liquid phase extraction below the critical point of the liquid interstitial phase.
[0018] In the context of the present invention, the term "skeleton" or "skeleton structure" refers to a network of interconnected oligomers, polymers or colloidal particles that form the solid structure of a gel or aerogel. The polymers or particles that make up the skeleton structure typically have a diameter of about 100 angstroms. However, the skeleton structure of the present invention may also include a network of interconnected oligomers, polymers or colloidal particles of all diameter sizes that form the solid structure within the gel or aerogel. Furthermore, the term "silica-based aerogel" or "silicon dioxide-based skeleton" refers to an aerogel skeleton in which silica comprises at least 50% by weight of the oligomers, polymers or colloidal particles that form the solid skeleton structure within the gel or aerogel.
[0019] In the context of the present invention, the term "aerogel composition" refers to any composite material that includes an aerogel material as a component of the composite. Examples of aerogel compositions include, but are not limited to: fiber-reinforced aerogel composites; aerogel composites that include additive elements such as opacifiers; aerogel-foam composites; aerogel-polymer composites; and composite materials in which aerogel particles, granules, granules, beads, or powders are incorporated into solid or semi-solid materials such as adhesives, resins, binders, foams, polymers, or similar solid materials.
[0020] In the context of the present invention, the term "single" refers to an aerogel material in which the majority (by weight) of the aerogel contained in the aerogel material or composition is in the form of a single interconnected aerogel nanostructure. A single aerogel material includes an aerogel material that is initially formed to have a single interconnected gel or aerogel nanostructure, but which is subsequently broken, fractured or fragmented into non-single aerogel nanostructures. Single aerogel materials are distinguished from particulate aerogel materials. The term "particulate aerogel material" refers to an aerogel material in which the majority (by weight) of the aerogel contained in the aerogel material is in the form of particles, granules, granules, beads, or powders, which can be combined or compressed together but lack interconnected aerogel nanostructures between individual particles.
[0021] In the context of the present invention, the term "reinforced aerogel composition" refers to an aerogel composition that includes a reinforcing phase (which is not part of the aerogel skeleton) within the aerogel material. The reinforcing phase can be any material that provides increased flexibility, elasticity, conformability or structural stability to the aerogel material. Examples of well-known reinforcing materials include, but are not limited to: open foam reinforcement materials, closed foam reinforcement materials, open film materials, honeycomb reinforcement materials, polymer reinforcement materials, and fiber reinforcement materials such as discrete fibers, woven materials, non-woven materials, cotton wool, mesh fabrics, mats, and felt products. In addition, fiber-based reinforcements can be combined with one or more other reinforcing materials and can be directed continuously throughout or in a limited preferred portion of the composition.
[0022] In the context of the present invention, the term "fiber-reinforced aerogel composition" refers to a reinforced aerogel composition comprising a fiber reinforcement material as a reinforcing phase. Examples of fiber reinforcement materials include, but are not limited to: discrete fibers, woven materials, non-woven materials, batting, mesh fabrics, mats, felts, or combinations thereof. Fiber reinforcement materials can include many materials, including, but not limited to: polyester, polyolefin terephthalate, polyethylene naphthalate, polycarbonate (e.g., rayon, nylon), cotton, (e.g., Lycra produced by DuPont), carbon (e.g., graphite), polyacrylonitrile (PAN), oxidized PAN, uncarbonized heat-treated PAN (such as those produced by SGL Carbon), glass-based materials (such as S-glass, 901 glass, 902 glass, 475 glass, E-glass), silica-based fibers such as quartz (e.g., Quaetzel produced by Saint-Gobain), Q-felt (produced by Johns Manville), Saffil (produced by Saffil), Durablanket (produced by Unifra x) and other silica fibers, Duraback (from Carborundum), polyaramid fibers such as Kevlar, Nomex, Sontera (all from DuPont), Conex (from Taijin), polyolefins such as Tyvek (from DuPont), Dyneema (from DSM), Spectra (from Honeywell), other polypropylene fibers such as Typar, Xavan (both from DuPont), fluoropolymers such as polytetrafluoroethylene (PTFE) with trade names such as Teflon (from DuPont), Goretex (from WLGORE), silicon carbide fibers such as Nicalon (COI Ceramics), ceramic fibers such as Nextel (3M), acrylic polymers, wool, silk, linen, leather, suede fibers, PBO-Zylon fibers (Tyobo), liquid crystal materials such as Vectan (Hoechst), Cambrelle fibers (DuPont), polyurethane, polyamide, wool fibers, boron, aluminum, iron, stainless steel fibers and other thermoplastics such as PEEK, PES, PEI, PEK, PPS.
[0023] As used herein, the term "aerogel blanket" or "aerogel blanket composition" refers to an aerogel composition that is reinforced with continuous sheets of reinforcing material. Aerogel blanket compositions are distinguished from other reinforced aerogel compositions that are reinforced with a discontinuous network of fibers or foams, such as discrete agglomerates or clusters of fibrous material. Aerogel blanket compositions are particularly useful in applications requiring flexibility because they are highly conformable and can be used like a blanket to cover surfaces of simple or complex geometries while retaining the excellent thermal insulation properties of aerogel. Aerogel blanket compositions and similar fiber-reinforced aerogel compositions are described in published U.S. Patent Application No. 2002 / 0094426 (paragraphs 12-16, 25-27, 38-58, 60-88), which are incorporated herein by reference for each section and paragraph cited.
[0024] In the context of the present invention, the term "wet gel" refers to a gel in which the mobile interstitial phase within the interconnected pore network primarily comprises a liquid phase such as a conventional solvent, a liquefied gas such as liquid carbon dioxide, or a combination thereof. Aerogels typically require initial preparation of a wet gel, followed by innovative processing and extraction to replace the mobile interstitial phase in the gel with air. Examples of wet gels include, but are not limited to, alcohol gels, hydrogels, keto gels, carbon gels, and any other wet gels known in the art.
[0025] In the context of the present invention, the term "additive" or "additive element" refers to a material that can be added to the aerogel composition before, during, or after the aerogel is made. Additives can be added to change or improve the desired properties of the aerogel, or to offset undesirable properties of the aerogel. Additives are typically added to the aerogel material before or during gelation. Examples of additives include, but are not limited to: microfibers, fillers, reinforcing agents, stabilizers, thickeners, elastic compounds, opacifiers, coloring or dyeing compounds, radiation absorbing compounds, radiation reflecting compounds, corrosion inhibitors, thermally conductive components, phase change materials, pH adjusters, redox adjusters, HCN moderators, exhaust moderators, conductive compounds, dielectric compounds, magnetic compounds, radar blocking components, hardeners, anti-shrinkage agents, and other aerogel additives known in the art. Other examples of additives include smoke suppressants and fire extinguishing agents. Published U.S. Patent Application No. 20070272902A1 (paragraphs
[0008] and
[0010] -
[0039] ) contains teachings of smoke suppressants and fire extinguishers, and is incorporated herein by reference for each individually cited paragraph.
[0026] As used herein, the term "flexible" or "flexibility" refers to the property of an aerogel material or composition that can be bent or flexed without macroscopic failure. The aerogel composition of the present invention is preferably capable of bending at least 5°, at least 25°, at least 45°, at least 65°, or at least 85° without macroscopic failure; and / or having a bending radius of less than 4 feet, less than 2 feet, less than 1 foot, less than 6 inches, less than 3 inches, less than 2 inches, less than 1 inch, less than 1 / 2 inch without macroscopic failure. Similarly, the term "highly flexible" or "highly flexible" refers to an aerogel material or composition that can be bent to at least 90° and / or has a bending radius of less than 1 / 2 inch without macroscopic failure. Furthermore, the term "classified flexible" and "classified as flexible" refers to an aerogel material or composition that is classified as flexible according to ASTM Classification Standard C1101 (ASTM International, West Conshohocken, PA).
[0027] The aerogel materials or compositions of the present invention may be flexible, highly flexible and / or categorically flexible. The aerogel materials or compositions of the present invention may also be drapable. In the context of the present invention, the term "drapable" or "drapability" refers to the property of an aerogel material or composition that can be bent or flexed to a bend radius of 90° or greater and about 4 inches or less without macroscopic failure. The aerogel materials or compositions of the present invention are preferably flexible so that the composition is non-rigid and can be applied and fitted to a three-dimensional surface or object, or pre-formed into a wide variety of shapes and configurations to simplify installation or application.
[0028] As used herein, the term "elastic" or "resilient" refers to the property of an aerogel material or composition to at least partially recover to its original form or dimensions after being compressed, flexed, or bent. The elasticity may be complete or partial, and it may be expressed as a percentage of recovery. The aerogel material or composition of the present invention preferably has an elasticity of more than 25%, more than 50%, more than 60%, more than 70%, more than 75%, more than 80%, more than 85%, more than 90%, or more than 95% recovery to its original form or dimensions after deformation. Similarly, the terms "classified elastic" and "classified as elastic" refer to an aerogel material or composition of the present invention that is classified as elastic according to ASTM Classification Standard C1101 (ASTM International, West Conshohocken, PA).
[0029] In the context of the present invention, the term "self-supporting" refers to the property of an aerogel material or composition that is flexible and / or resilient primarily due to the physical properties of the aerogel and any reinforcing phase in the aerogel composition. The self-supporting aerogel material or composition of the present invention is distinguished from other aerogel materials, such as coatings, which rely on an underlying substrate to provide flexibility and / or resiliency to the material.
[0030] In the context of the present invention, the term "shrinkage" refers to the ratio of: 1) the difference between the measured final density of a dried aerogel material or composition, or an aerogel-like material or composition, and the target density calculated from the solid content of the sol-gel precursor solution, relative to 2) the target density calculated from the solid content of the sol-gel precursor solution. Shrinkage can be calculated by the following formula: Shrinkage = [Final density (g / cm 3 )-target density (g / cm 3 )] / [Target density (g / cm 3 )]. The shrinkage of the aerogel material of the present invention is preferably 50% or less, 25% or less, 10% or less, 8% or less, 6% or less, 5% or less, 4% or less, 3% or less, 2% or less, 1% or less, 0.1% or less, about 0.01% or less, or a range between any two of these values.
[0031] In the context of the present invention, the term "thermal conductivity" or "TC" refers to a measure of the ability of a material or composition to transfer heat between two surfaces on either side of the material or composition under a temperature difference between the two surfaces. Thermal conductivity is specifically measured as the heat energy transferred per unit time and per unit surface area, divided by the temperature difference. It is usually reported in SI units of mW / m*K (milliwatt per meter*Kelvin). The thermal conductivity of a material may be determined by methods known in the art, including, but not limited to: Steady State Heat Transfer Properties Test by Heat Flow Meter Apparatus (ASTM C518, ASTM International, West Conshohocken, PA); Steady State Heat Flux Measurement and Heat Transfer Properties Test by Guarded Hot Plate Apparatus (ASTM C177, ASTM International, West Conshohocken, PA); Steady State Heat Transfer Properties Test for Pipe Insulation (ASTM C335, ASTM International, West Conshohocken, PA); Thin Heater Thermal Conductivity Test (ASTM C1114, ASTM International, West Conshohocken, PA); Determination of Thermal Resistance by Guarded Hot Plate Apparatus and Heat Flow Meter Method (EN12667, British Standards institution, United Kingdom); or Determination of Steady State Thermal Resistance and Related Properties - Guarded Hot Plate Apparatus (ISO8203, International Organization for Standardization, Switzerland). In the context of the present invention, thermal conductivity measurements are taken at a temperature of about 37.5°C and a compression of about 2 psi according to ASTM C177 or ASTM C518 standards, unless otherwise stated. The aerogel materials or compositions of the present invention preferably have a thermal conductivity of about 50 mW / mK or less, about 40 mW / mK or less, about 30 mW / mK or less, about 25 mW / mK or less, about 20 mW / mK or less, about 18 mW / mK or less, about 16 mW / mK or less, about 14 mW / mK or less, about 12 mW / mK or less, about 10 mW / mK or less, about 5 mW / mK or less, or a range between any two of these values.
[0032] In the context of the present invention, the term "density" refers to the mass per unit volume of an aerogel material or composition. The term "density" generally refers to the actual density of the aerogel material, as well as the overall density of the aerogel composition. Density is generally measured in kg / m 3or g / cc. The density of an aerogel material or composition may be determined by methods known in the art, including, but not limited to: Standard Test Method for Dimensions and Density of Preformed Block and Board Thermal Insulation (ASTM C303, ASTM International, West Conshohocken, PA); Standard Test Method for Thickness and Density of Felt or Batt Thermal Insulation (ASTM C167, ASTM International, West Conshohocken, PA); or Determination of Apparent Density of Preformed Pipe Insulation (ISO 18098, International Organization for Standardization, Switzerland). In the context of the present invention, density measurements are obtained in accordance with ASTM C167 unless otherwise specified. The aerogel materials or compositions of the present invention preferably have a density of about 0.60 g / cc or less, about 0.50 g / cc or less, about 0.40 g / cc or less, about 0.30 g / cc or less, about 0.25 g / cc or less, about 0.20 g / cc or less, about 0.18 g / cc or less, about 0.16 g / cc or less, about 0.14 g / cc or less, about 0.12 g / cc or less, about 0.10 g / cc or less, about 0.05 g / cc or less, about 0.01 g / cc or less, or a range between any two of these values.
[0033] In the context of the present invention, the term "hydrophobicity" refers to a measure of the ability of an aerogel material or composition to repel water.
[0034] The hydrophobicity of an aerogel material or composition can be expressed as water absorption. In the context of the present invention, the term "water absorption" refers to a measure of the potential of an aerogel material or composition to absorb or retain water. Water absorption can be expressed as the percentage (by weight or volume) of water absorbed or retained by an aerogel material or composition when exposed to water under certain measurement conditions. The water absorption of an aerogel material or composition can be determined by methods known in the art, including, but not limited to: Standard Test Method for Measuring Water Retention (Drainage) Properties of Fiberglass Insulation (ASTM C1511, ASTM International, West Conshohocken, PA); Standard Test Method for Water Absorption of Thermal Insulation Materials by Immersion (ASTM C1763, ASTM International, West Conshohocken, PA); Thermal Insulation Products for Building Applications: Measurement of Short-Term Water Absorption by Partial Immersion (EN 1609, British Standardsinstitution, United Kingdom). In the context of the present invention, water absorption measurements are obtained according to ASTM C1511 at atmospheric pressure and temperature unless otherwise specified. The aerogel material or composition of the present invention preferably has a water absorption according to the ASTM C1511 standard of about 100 wt% or less, about 80 wt% or less, about 60 wt% or less, about 50 wt% or less, about 40 wt% or less, about 30 wt% or less, about 20 wt% or less, about 15 wt% or less, about 10 wt% or less, about 8 wt% or less, about 3 wt% or less, about 2 wt% or less, about 1 wt% or less, about 0.1 wt% or less, or a range between any two of these values. Aerogel materials or compositions of the present invention may have a water absorption according to ASTM C1763 of about 100 wt% or less, about 80 wt% or less, about 60 wt% or less, about 50 wt% or less, about 40 wt% or less, about 30 wt% or less, about 20 wt% or less, about 15 wt% or less, about 10 wt% or less, about 8 wt% or less, about 3 wt% or less, about 2 wt% or less, about 1 wt% or less, about 0.1 wt% or less, or a range between any two of these values. An aerogel material or composition having an improved water absorption relative to another aerogel material or composition will have a lower water absorption percentage than a reference aerogel material or composition.
[0035] The hydrophobicity of an aerogel material or composition can be expressed as water vapor absorption. As used herein, the term "water vapor absorption" refers to a measure of the potential of an aerogel material or composition to absorb or retain water. Water absorption can be expressed as the percentage (by weight) of water vapor absorbed or retained by an aerogel material or composition when exposed to water vapor under certain measurement conditions. The water vapor absorption of an aerogel material or composition can be determined by methods known in the art, including, but not limited to, Standard Test Method for Water Vapor Absorption of Surface Untreated Mineral Fiber Insulation (ASTM C1104, ASTM International, West Conshohocken, PA). As used herein, water vapor absorption measurements are obtained at atmospheric pressure and temperature in accordance with ASTM C1104 unless otherwise indicated. The aerogel materials or compositions of the present invention preferably may have a water vapor absorption of about 50 wt% or less, about 40 wt% or less, about 30 wt% or less, about 20 wt% or less, about 15 wt% or less, about 10 wt% or less, about 8 wt% or less, about 3 wt% or less, about 2 wt% or less, about 1 wt% or less, about 0.1 wt% or less, or a range between any two of these values. An aerogel material or composition having an improved water vapor absorption relative to another aerogel material or composition may have a lower water vapor absorption / water vapor retention percentage than a reference aerogel material or composition.
[0036] The hydrophobicity of an aerogel material or composition can be represented by measuring the equilibrium contact angle of a water droplet at the interface with the surface of the material. The aerogel material or composition of the present invention can have a water contact angle of about 90° or greater, about 120° or greater, about 130° or greater, about 140° or greater, about 150° or greater, about 160° or greater, about 170° or greater, about 175° or greater, or a range between any two of these values.
[0037] As used herein, the term "heat of combustion" or "HOC (heat of combustion)" refers to a measure of the amount of heat energy released by the combustion of an aerogel material or composition. Heat of combustion is typically reported as calories of heat energy released per gram of aerogel material or composition (cal / g), or megajoules of heat energy released per kilogram of aerogel material or composition (MJ / kg). The heat of combustion of an aerogel material or composition may be determined by methods known in the art, including, but not limited to: fire test reaction of the product - measuring the total heat of combustion (calorific value) (ISO 1716, International Organization for Standardization, Switzerland). As used herein, heat of combustion measurements are obtained according to conditions comparable to the ISO 1716 standard, unless otherwise specified. Aerogel materials or compositions of the present invention preferably may have a heat of combustion of about 750 cal / g or less, about 717 cal / g or less, about 700 cal / g or less, about 650 cal / g or less, about 600 cal / g or less, about 575 cal / g or less, about 550 cal / g or less, about 500 cal / g or less, about 450 cal / g or less, about 400 cal / g or less, about 350 cal / g or less, about 300 cal / g or less, about 250 cal / g or less, about 200 cal / g or less, about 150 cal / g or less, about 100 cal / g or less, about 50 cal / g or less, about 25 cal / g or less, about 10 cal / g or less, or a range between any two of these values. An aerogel composition having an improved heat of combustion relative to another aerogel composition may have a lower heat of combustion value than the reference aerogel composition.
[0038] In the context of the present invention, "thermal decomposition initiation of hydrophobic organic material", "thermal decomposition initiation" and "T d The term "onset of thermal decomposition of a material or composition" refers to the lowest temperature measurement in the environment from the rapid exothermic reaction of decomposition of a hydrophobic organic material occurring within the material or composition. The onset of thermal decomposition of a material or composition can be measured using thermogravimetric analysis (TGA). A TGA curve of a material is a graph that plots the weight loss (% mass) of a material when it is exposed to increasing ambient temperature. The onset of thermal decomposition of a material is associated with the intersection of the following tangent lines of the TGA curve: a line tangent to the bottom line of the TGA curve, and a line tangent to the TGA curve at the point of maximum slope during the rapid decomposition event associated with decomposition of the hydrophobic organic material. Within the context of the present invention, measurements of the onset of thermal decomposition of a hydrophobic organic material are obtained using TGA analysis as provided in this paragraph, unless otherwise specified.
[0039] The onset of thermal decomposition of a material can also be measured using differential scanning calorimetry (DSC) analysis. A DSC curve for a material depicts the heat energy (mW / mg) released by a material when it is exposed to gradually increasing ambient temperatures. The onset of thermal decomposition temperature of a material can be correlated to the DSC curve where the ΔmW / mg (change in heat energy output) increases the most, thus representing the heat output from the exotherm of the aerogel material. Within the context of the present invention, measurements of the onset of thermal decomposition using DSC are obtained using a temperature ramp rate of 20°C / min or less, unless otherwise stated.
[0040] The aerogel materials or compositions of the present invention preferably have a thermal decomposition onset of about 100°C or greater, about 150°C or greater, about 200°C or greater, about 250°C or greater, about 300°C or greater, about 350°C or greater, about 400°C or greater, about 450°C or greater, about 500°C or greater, about 550°C or greater, about 600°C or greater, about 650°C or greater, about 700°C or greater, about 750°C or greater, about 800°C or greater, or a range between any two of these values. An aerogel material or composition having an improved onset of thermal decomposition relative to another aerogel material or composition will have a higher onset of thermal decomposition temperature than the reference aerogel material or composition.
[0041] In the context of the present invention, the term "self-heating temperature" refers to a measure of the lowest temperature of ambient heat at which an exothermic reaction occurs under specified measurement conditions within an insulation system, such as an insulation system including an aerogel material or composition. In the context of the present invention, the self-heating temperature of an insulation system is measured according to the following procedure, unless otherwise specified: a) providing an insulation system having a geometric cube with a dimension of 20 mm on each side; b) placing a thermocouple measuring device at the center of the insulation system; and c) exposing the insulation system to a series of increasing temperatures until a self-heating exothermic event occurs, which is indicated by the temperature of the thermocouple measuring device exceeding the external exposure temperature of the specimen by an amount significant enough to indicate a self-heating exothermic event within the insulation system. Preferably, the aerogel materials or compositions of the present invention preferably have a self-heating temperature of about 100°C or more, about 150°C or more, about 200°C or more, about 250°C or more, about 300°C or more, about 350°C or more, about 400°C or more, about 450°C or more, about 500°C or more, about 550°C or more, about 600°C or more, about 650°C or more, about 700°C or more, about 750°C or more, about 800°C or more, or a range between any two of these values. An aerogel material or composition having an improved self-heating temperature relative to another aerogel material or composition will have a higher self-heating temperature than the reference aerogel material or composition.
[0042] Aerogels are described as a framework of interconnected structures that most often include interconnected oligomeric, polymeric, or colloidal particles. Aerogel frameworks can be made from a variety of precursor materials, including: inorganic precursor materials (such as those used to make silica-based aerogels); organic precursor materials (such as those used to make carbon-based aerogels); hybrid inorganic / organic precursor materials; and combinations thereof. In the context of the present invention, the term "hybrid aerogel" refers to an aerogel made from a combination of two or more different aerogel precursors.
[0043] Inorganic aerogels are usually formed from metal oxide or metal alkoxide materials. The metal oxide or metal alkoxide material can be an oxide or alkoxide based on any metal that can form an oxide. The metals include, but are not limited to: silicon, aluminum, titanium, zirconium, hafnium, yttrium, vanadium, cerium, etc. Inorganic silica aerogels are traditionally made by hydrolysis and condensation of silica-based alkoxides (such as tetraethoxysilane), or by gelation of silicic acid or water glass. Other relevant inorganic precursor materials for the synthesis of silica-based aerogels include, but are not limited to: metal silicates such as sodium silicate or potassium silicate, alkoxysilanes, partially hydrolyzed alkoxysilanes, tetraethoxysilane (TEOS), partially hydrolyzed TEOS, condensation polymers of TEOS, tetramethoxysilane (TMOS), partially hydrolyzed TMOS, condensation polymers of TMOS, tetra-n-propoxysilane, partially hydrolyzed and / or condensation polymers of tetra-n-propoxysilane, polyethyl silicate, partially hydrolyzed polyethyl silicate, monoalkyl alkoxysilanes, bis-trialkoxyalkyl or aryl silanes, polyhedral silsesquioxanes, or combinations thereof.
[0044] In certain embodiments of the present invention, pre-hydrolyzed TEOS, such as Silbond H-5 (SBH5, Silbond), which is hydrolyzed at a water / silicon dioxide ratio of about 1.9-2, can be used as commercially available or can be further hydrolyzed before being incorporated into the gelation process. Partially hydrolyzed TEOS or TMOS, such as polyethyl silicate (Silbond 40) or polymethyl silicate, can also be used as commercially available or can be further hydrolyzed before being incorporated into the gelation process.
[0045] Inorganic aerogels may also include a gel precursor including at least one hydrophobic group, such as an alkyl metal alkoxide, a cycloalkyl metal alkoxide, and an aryl metal alkoxide, which may impart or improve certain properties of the gel such as stability and hydrophobicity. Inorganic silica aerogels may specifically include a hydrophobic precursor such as an alkyl silane or an aryl silane. The hydrophobic gel precursor may be used as the main precursor material to form the skeleton of the gel material. However, the hydrophobic gel precursor is more commonly used as a co-precursor in combination with a simple metal alkoxide to form a hybrid aerogel. The hydrophobic inorganic precursor materials for the synthesis of silica-based aerogels include, but are not limited to: trimethylmethoxysilane [TMS], dimethyldimethoxysilane [DMS], methyltrimethoxysilane [MTMS], trimethylethoxysilane, dimethyldiethoxysilane [DMDS], methyltriethoxysilane [MTES], ethyltriethoxysilane [ETES], diethyldiethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane [PhTES], hexamethyldisilazane and hexaethyldisilazane, etc.
[0046] Aerogels can be treated to impart or improve hydrophobicity. The hydrophobic treatment can be applied to the sol-gel solution, the wet gel, or to the aerogel after liquid extraction before liquid extraction. Hydrophobic treatment is particularly commonly used in the manufacture of metal oxide aerogels, such as silica aerogels. Examples of hydrophobic treatment of gels are described in detail below, particularly in the text of treating wet silica gels. However, the specific examples and descriptions provided herein are not intended to limit the scope of the present invention to any particular type of hydrophobic treatment procedure or aerogel substrate. The present invention may include any gel or aerogel known in the art, as well as related methods for hydrophobic treatment of aerogels (in wet gel form or dried aerogel form).
[0047] The hydrophobic treatment is performed by reacting the hydroxyl moieties on the gel, such as the silanol groups (Si-OH) present on the backbone of the silica gel, with the functional groups of the hydrophobicizing agent. The resulting reaction converts the silanol groups and the hydrophobicizing agent into hydrophobic groups on the backbone of the silica gel. The hydrophobicizing agent compound and the hydroxyl groups on the gel can be reacted according to the following reaction: R N MX 4-N (Hydrophobic agent) + MOH (Silanol) → MOMR N (Hydrophobic groups) + HX. The hydrophobic treatment can occur both on the external large surfaces of the silica gel, and on the internal pore surfaces within the porous network of the gel.
[0048] The gel may be soaked in a mixture of a hydrophobizing agent and an optional hydrophobizing treatment solvent in which the hydrophobizing agent is soluble and which is also miscible with the gel solvent in the wet gel. A wide range of hydrophobizing treatment solvents may be used, including solvents such as methanol, ethanol, isopropanol, xylene, toluene, benzene, dimethylformamide, and hexane. The hydrophobizing agent in liquid or gaseous form may also be directly contacted with the gel to impart hydrophobicity.
[0049] The hydrophobic treatment process may include mixing or stirring to help the hydrophobic agent penetrate the wet gel. The hydrophobic treatment process may also include changing other conditions such as temperature and pH to further enhance or optimize the treatment reaction. After the reaction is completed, the wet gel is rinsed to remove unreacted compounds and reaction byproducts.
[0050] The hydrophobizing agent for hydrophobic treatment of aerogel is generally of the formula: R N MX 4-N Compound; wherein M is a metal; R is a hydrophobic group such as CH3, CH2CH3, C6H6, or a similar hydrophobic alkyl, cycloalkyl, or aryl moiety; and X is a halogen, typically Cl. Specific examples of hydrophobicizing agents include, but are not limited to: trimethylchlorosilane [TMCS], triethylchlorosilane [TECS], triphenylchlorosilane [TPCS], dimethylchlorosilane [DMCS], dimethyldichlorosilane [DMDCS], and the like. The hydrophobicizing agent may also have the formula: Y(R3M)2; wherein M is a metal; Y is a bridging group such as NH or O; and R is a hydrophobic group such as CH3, CH2CH3, C6H6, or a similar hydrophobic alkyl, cycloalkyl, or aryl moiety. Specific examples of the hydrophobicizing agent include, but are not limited to: hexamethyldisilazane [HMDZ] and hexamethyldisiloxane [HMDSO]. The hydrophobicizing agent may further include the formula: R N MV 4-N wherein V is a reactive or leaving group other than a halogen. Specific examples of the hydrophobizing agent include, but are not limited to, vinyl triethoxysilane and vinyl trimethoxysilane.
[0051] In the context of the present invention, the term "hydrophobic bound silicon" refers to silicon atoms in the backbone of a gel or aerogel that include at least one hydrophobic group covalently bonded to the silicon atom. Examples of hydrophobic bound silicon include, but are not limited to, silicon atoms in silica groups in the backbone of a gel formed by a gel precursor that includes at least one hydrophobic group (such as MTES or DMDS). Hydrophobic bound silicon may also include, but are not limited to, silicon atoms in the backbone of a gel or on the surface of a gel that have been treated with a hydrophobizing agent (such as HMDZ) to impart or improve hydrophobicity by incorporating other hydrophobic groups into the composition. The hydrophobic groups of the present invention include, but are not limited to, methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, octyl, phenyl, or other substituted or unsubstituted hydrophobic organic groups known in the art. In the context of the present invention, the terms "hydrophobic groups", "hydrophobic organic materials", and "hydrophobic organic content" specifically exclude the easily hydrolyzable organically bound silane groups on the backbone of the gel material that are reaction products between organic solvents and silanol groups.
[0052] In the context of the present invention, the terms "aliphatic hydrophobic groups", "aliphatic hydrophobic organic materials", and "aliphatic hydrophobic organic content" refer to hydrophobic groups on hydrophobic silicon that are limited to aliphatic hydrocarbons, including, but not limited to, hydrocarbon moieties (but non-aromatic) containing 1-40 carbon atoms that may be saturated or unsaturated, which may include linear, branched, cyclic moieties (including fused, bridged, and spiro-fused polycyclics), or combinations thereof, such as alkyl, alkenyl, alkynyl, (cycloalkyl)alkyl, (cycloalkenyl)alkyl, or (cycloalkyl)alkenyl moieties, and hetero-aliphatic moieties (wherein one or more carbon atoms are independently substituted with one or more atoms selected from the group consisting of oxygen, sulfur, nitrogen, and phosphorus). In certain embodiments of the present invention, at least 50% of the hydrophobic organic materials in the aerogel composition include aliphatic hydrophobic groups.
[0053] NMR spectra such as CP / MAS can be used 29 Si solid-state NMR analysis of the amount of hydrophobic bound silica contained in the aerogel. NMR analysis of the aerogel can characterize and relatively quantify: M-type hydrophobic bound silica (monofunctional silica, such as TMS derivatives); D-type hydrophobic bound silica (difunctional silica, such as DMDS derivatives); T-type hydrophobic bound silica (trifunctional silica, such as MTES derivatives); and Q-type hydrophobic bound silica (tetrafunctional silica, such as TEOS derivatives). NMR analysis can also be performed by classifying specific types of hydrophobic bound silica into sub-types (e.g., T-type hydrophobic bound silica is classified into T-type hydrophobic bound silica, and ... 1 Species, T 2 Species, and T 3Species) were used to analyze the bonding chemistry of hydrophobically bound silicon contained in aerogels. Specific details on NMR analysis of silica materials are found in the paper "Application of solid-state NMR to study organic / inorganic multi-component materials" by Geppi et al., specifically pages 7-9 (Appl. Spec. Rev. (2008), 44-1: 1-89), which is incorporated herein by reference according to the specific page number cited.
[0054] CP / MAS 29 The hydrophobicity of the bound silica in SiNMR analysis can be characterized based on the following chemical shift peaks: M 1 (30 to 10 ppm); D 1 (10 to -10 ppm), D 2 (-10 to -20ppm); T 1 (-30 to -40ppm), T 2 (-40 to -50ppm), T 3 (-50 to -70ppm); Q 2 (-70 to -85ppm), Q 3 (-85 to -95ppm), Q 4 (-95 to -110 ppm). These chemical shift peaks are approximate and exemplary and are not intended to be limiting or defining. The exact chemical shift peaks attributable to the various silicon species within a material depend on the specific chemical composition of the material and can generally be decoded through routine experimentation and analysis in the art.
[0055] The aerogel material of the present invention may have a T between about 0.01 and about 0.5, between about 0.01 and about 0.3, or between about 0.1 and about 0.3. 1-2 :T 3 The ratio of T 1-2 :T 3 The ratio of T 1 With T 2 The combination of species relative to T 3 The ratio of species. 1 , T 2 and T 3 The amount can be obtained by 29 The T as defined above in Si NMR analysis 1 Species, T 2 Species or T 3 The integration of the individual chemical shift peaks associated with the species is quantified. The aerogel material of the present invention may have a Q between about 0.1 and 2.5, between about 0.1 and 2.0, between about 0.1 and 1.5, between about 0.1 and 1.0, or between about 0.5 and 1.0. 2-3 :Q 4 The ratio of Q2-3 :Q 4 The ratio of Q 2 With Q 3 The combination of species relative to Q 4 The ratio of species. 2 , Q 3 and Q 4 The amount can be obtained by 29 The Q as defined above in Si NMR analysis 2 Species, Q 3 Species or Q 4 The integration of individual chemical shift peaks associated with the species is quantified.
[0056] In the context of the present invention, the term "hydrophobic organic content" refers to the amount of hydrophobic organic material bound to the backbone of an aerogel material or composition. The hydrophobic organic content of an aerogel material or composition can be expressed as the weight percentage of the amount of hydrophobic organic material on the backbone of the aerogel relative to the total amount of material of the aerogel material or composition. The hydrophobic organic content can be calculated based on the nature and relative concentrations of the materials used to make the aerogel material or composition as is well known in the art. The hydrophobic organic content can also be measured using thermogravimetric analysis (TGA) in an inert atmosphere. More specifically, the percentage of hydrophobic organic material in the aerogel can be related to the percentage of weight loss of the aerogel material or composition when the combustion heat temperature is applied during the TGA analysis, adjusting for moisture loss, residual solvent loss, and loss of readily hydrolyzable alkoxy groups during the TGA analysis.
[0057] The aerogel materials or compositions of the present invention may have a hydrophobic organic content of 50 wt % or less, 40 wt % or less, 30 wt % or less, 25 wt % or less, 20 wt % or less, 15 wt % or less, 10 wt % or less, 8 wt % or less, 6 wt % or less, 5 wt % or less, 4 wt % or less, 3 wt % or less, 2 wt % or less, 1 wt % or less, or a range between any two of these values.
[0058] The term "fuel content" refers to the total amount of combustible material in an aerogel material or composition, which can be related to the total percentage of weight loss of the aerogel material or composition under adjusted moisture loss when the heat of combustion is applied during TGA or TG-DSC analysis. The fuel content of the aerogel material or composition can include hydrophobic organic content, as well as other combustible materials such as residual alcohol solvents, filler materials, reinforcing materials, and alkoxy groups that can be easily hydrolyzed.
[0059] Organic aerogels are usually formed from carbon-based polymer precursors. The polymer materials include, but are not limited to: resorcinol (RF), polyimide, polyacrylate, polymethacrylate, acrylate oligomer, polyalkylene oxide, polyurethane, polyphenol, polybutane, terminal trialkoxy silyl polydimethylsiloxane, polystyrene, polyacrylonitrile, polyfurfural, melamine formaldehyde, cresol formaldehyde, phenol furfural, polyether, polyol, polyisocyanate, polyhydroxybenzene, polyvinyl alcohol dialdehyde, polycyanurate, polyacrylamide, various epoxides, agar, agarose, chitosan, and combinations thereof. For example, organic RF aerogels are usually made by sol-gel polymerization of resorcinol or melamine with formaldehyde under alkaline conditions.
[0060] Organic / inorganic hybrid aerogels mainly include organosiloxane film (organically modified silica) aerogels. These organosiloxane film materials contain organic components covalently bonded to the silica network. Organosiloxane films are usually formed by hydrolysis and condensation of organically modified silane, R-Si(OX)3, and traditional alkoxide precursors, Y(OX)4. In these formulas, X can represent, for example, CH3, C2H5, C3H7, C4H9; Y can represent, for example, Si, Ti, Zr, or Al; and R can be any organic fragment such as methyl, ethyl, propyl, butyl, isopropyl, methacrylate, acrylate, vinyl, epoxide, etc. The organic components in the organosiloxane film aerogel can also be dispersed throughout the silica network or chemically bonded to the silica network.
[0061] In the context of the present invention, the term "organosiloxane film" includes the foregoing materials as well as other organically modified ceramics, sometimes referred to as "ormocers". Organosiloxane films are often used as coatings, wherein the organosiloxane film is cast on a substrate via, for example, a sol-gel process. Examples of other organic-inorganic hybrid aerogels of the present invention include, but are not limited to, silica-polyethers, silica-PMMA, silica-chitosan, carbides, nitrides, and other combinations of the foregoing organic and inorganic aerogel-forming compounds. U.S. Patent Application Publication No. 20050192367 (paragraphs
[0022] -
[0038] and
[0044] -
[0058] ) contains teachings of such hybrid organic-inorganic materials, which are incorporated herein by reference in their respective cited sections and paragraphs.
[0062] The aerogel of the present invention is preferably an inorganic silica aerogel formed mainly from an alcohol solution of a hydrolyzed silicate (formed from a silicon alkoxide). However, the present invention as a whole can be implemented with any other aerogel composition known in the art, and is not limited to any one precursor material or a mixture of precursor materials.
[0063] The manufacture of aerogels generally comprises the following steps: i) forming a sol-gel solution; ii) forming a gel from the sol-gel solution; and iii) extracting a solvent from the gel material via innovative processing and extraction to obtain a dry aerogel material. This process is described in detail below, particularly in the context of forming inorganic aerogels such as silica aerogels. However, the specific examples and descriptions provided herein are not intended to limit the scope of the present invention to any particular type of aerogel and / or preparation method. The present invention may include any aerogel formed by any relevant preparation method known in the art.
[0064] The first step in forming an inorganic aerogel is typically to form a sol-gel solution via the hydrolysis and condensation of a metal alkoxide precursor in an alcohol-based solvent. The major variables in forming an inorganic aerogel include the type of alkoxide precursor contained in the sol-gel solution, the nature of the solvent, the processing temperature and pH of the sol-gel solution (which can be altered by the addition of acid or base), and the precursor / solvent / water ratio within the sol-gel solution. Control of these variables in forming the sol-gel solution can control the growth and aggregation of the gel skeleton during the subsequent transition of the gel material from the "sol" state to the "gel" state. Although the properties of the resulting aerogel are affected by the pH of the precursor solution and the molar ratio of the reactants, any pH and any molar ratio that can form a gel can be used in the present invention.
[0065] The sol-gel solution is formed by combining at least one gelling precursor with a solvent. Suitable solvents for use in forming the sol-gel solution include lower alcohols having 1 to 6, preferably 2 to 4 carbon atoms, although other solvents known to those skilled in the art may be used. Examples of solvents that may be used include, but are not limited to: methanol, ethanol, isopropanol, ethyl acetate, ethyl acetoacetate, acetone, dichloromethane, tetrahydrofuran, and the like. A variety of solvents may also be combined to achieve the desired degree of dispersion and optimize the properties of the gel material. The selection of the optimized solvent for the sol-gel and the gel forming step therefore depends on the specific precursors, fillers and additives incorporated into the sol-gel solution; as well as the target processing conditions for gelation and liquid phase extraction, and the desired properties of the final aerogel material.
[0066] Water may also be present in the precursor-solvent solution. Water may dissolve the metal alkoxide precursor into the metal hydroxide precursor. The hydrolysis reaction may be (using TEOS in an ethanol solvent as an example): Si(OC2H5)4+4H2O→Si(OH)4+4(C2H5OH). The resulting hydrolyzed metal hydroxide precursor is still in a "sol" state, with individual molecules or small aggregated (or oligomeric) colloidal clusters of molecules suspended in the solvent solution. For example, the polymerization / condensation reaction of the Si(OH)4 precursor may occur as follows: 2Si(OH)4=(OH)3Si-O-Si(OH)3+H2O. This polymerization reaction may be continued until colloidal clusters of polymerized (or oligomeric) SiO2 (silicon dioxide) molecules are formed.
[0067] Acids and bases can be incorporated into the sol-gel solution to control the pH of the solution and to catalyze the hydrolysis and condensation reactions of the precursor materials. Although any acid can be used to catalyze the precursor reaction and obtain a solution with a lower pH, preferred acids include: HCl, H2SO4, H3PO4, oxalic acid and acetic acid. Any base can also be used to catalyze the precursor reaction and obtain a solution with a higher pH, and preferred bases include NH4OH.
[0068] The sol-gel solution may contain other co-gelation precursors, as well as filler materials and other additives. The filler materials and other additives may be distributed to the sol-gel solution at any point before or during gel formation. The filler materials and other additives may also be incorporated into the gel material after colloidization via various techniques known in the art. The sol-gel solution comprising gelation precursors, solvents, catalysts, water, filler materials and other additives is preferably a uniform solution that can effectively form a gel under suitable conditions.
[0069] Once the sol-gel solution is formed and optimized, the gel-forming components in the sol-gel can be converted into a gel material. The process of converting the gel-forming components into a gel material includes an initial gel formation step, in which the gel is cured until the gel point of the gel material. The gel point of the gel material can be considered to be the point at which the gelled solution exhibits resistance to flow and / or forms a substantially continuous polymer backbone throughout its volume. Many gel formation techniques are known in the art. Examples include, but are not limited to: keeping the mixture in a static state for a sufficient period of time; adjusting the pH of the solution; adjusting the temperature of the solution; directing a form of energy to the mixture (ultraviolet light, visible light, infrared light, microwaves, ultrasound, particle radiation, electromagnetic waves); or a combination thereof.
[0070] The process of converting the gel-forming ingredients into a gel material may also include an aging step (also known as curing) prior to liquid phase extraction. Aging the gel material after reaching its gel point can further strengthen the gel skeleton by increasing the number of crosslinks within the network. The gel aging period can be adjusted to control various properties within the resulting aerogel material. This aging procedure can be used to prevent potential volume loss and shrinkage during liquid phase extraction. Aging can include: keeping the gel in a quiescent state (before extraction) for an extended period of time; keeping the gel at an elevated temperature; adding a crosslinking promoting compound; or any combination thereof. The preferred temperature for aging is generally between about 10°C and about 100°C. Aging of the gel material is generally continued until liquid phase extraction of the wet gel material.
[0071] The time for the gel-forming component to be converted into a gel material includes the period of initial gel formation (from the start of gelation until the gel point), and any subsequent solidification and aging of the gel material before liquid phase extraction (from the gel point until the start of liquid phase extraction). The total time for the gel-forming component to be converted into a gel material is generally from about 1 minute to several days, preferably about 30 hours or less, about 24 hours or less, about 15 hours or less, about 10 hours or less, about 6 hours or less, about 4 hours or less, about 2 hours or less, about 1 hour or less, about 30 minutes or less, or about 15 minutes or less.
[0072] The obtained gel material can be washed with a suitable second solvent to replace the first reaction solvent present in the wet gel. The second solvent can be a linear monoalcohol having one or more aliphatic carbon atoms, a diol having two or more carbon atoms, a branched alcohol, a cyclic alcohol, an alicyclic alcohol, an aromatic alcohol, a polyol, an ether, a ketone, a cyclic ether or a derivative thereof.
[0073] Once the gel material is formed and processed, the liquid phase of the gel can be at least partially extracted from the wet gel using extraction methods (including innovative processing and extraction techniques) to form an aerogel material. Among them, liquid phase extraction plays an important role in the engineering of aerogel characteristics, such as porosity and density, and related properties such as thermal conductivity. Typically, aerogels are obtained when the liquid phase is extracted from the gel in a manner that causes little shrinkage of the porous network and skeleton of the wet gel.
[0074] Aerogels are typically formed by removing a liquid mobile phase from a gel material at a temperature and pressure near or above the critical point of the liquid mobile phase. Once the critical point is reached (near critical) or exceeded (supercritical) (i.e., the pressure and temperature of the system are at or above the critical pressure and critical temperature, respectively), a new supercritical phase appears in the liquid that is distinct from the liquid or gas phase. The solvent can then be removed without the introduction of liquid-gas interfaces, capillary pressures, or any related mass transfer restrictions typically associated with liquid-gas boundaries. In addition, the supercritical phase is typically more miscible with organic solvents and therefore has better extraction capabilities. Co-solvents and solvent exchange are also commonly used to optimize supercritical fluid drying processes.
[0075] If evaporation or extraction occurs below the supercritical point, the capillary forces generated by the evaporation of the liquid will cause the pores in the gel material to shrink and the skeleton to collapse. Keeping the mobile phase near or above the critical pressure and temperature during the solvent extraction process reduces the negative effects of such capillary forces. In certain embodiments of the present invention, the use of near-critical conditions just below the critical point of the solvent system can produce aerogel materials or compositions with sufficiently low shrinkage, thereby producing a commercially viable end product.
[0076] Several other aerogel extraction techniques are known in the art, including many different methods of using supercritical fluids to dry aerogels. For example, Kistler (J. Phys. Chem. (1932) 36:52-64) describes a simple supercritical extraction process in which the gel solvent is maintained above its critical pressure and temperature, thereby reducing capillary forces for evaporation and maintaining the structural integrity of the gel network. U.S. Patent No. 4,610,863 describes an extraction process in which the gel solvent is exchanged for liquid carbon dioxide and subsequently extracted under conditions in which the carbon dioxide is in a supercritical state. U.S. Patent No. 6,670,402 teaches the production of aerogels by extracting a liquid phase from a gel via rapid solvent exchange by injecting supercritical (but not liquid) carbon dioxide into an extractor that has been preheated and prepressurized to substantially supercritical conditions or above. U.S. Patent No. 5,962,539 describes a process for obtaining an aerogel from a polymer material in sol-gel form in an organic solvent by exchanging an organic solvent for a fluid having a critical temperature below the polymer decomposition temperature, and supercritically extracting the fluid / sol-gel. U.S. Patent No. 6,315,971 discloses a process for making a gel composition comprising: drying a wet gel comprising gel solids and a desiccant to remove the desiccant under drying conditions sufficient to reduce shrinkage of the gel during drying. U.S. Patent No. 5,420,168 describes a process in which a resorcinol / formaldehyde aerogel can be made using a simple air drying procedure. U.S. Patent No. 5,565,142 describes a drying technique in which the gel surface is modified to be stronger and more hydrophobic so that the gel skeleton and pores can resist collapse during ambient drying or subcritical extraction. Other examples of extracting a liquid phase from an aerogel material can be found in U.S. Patent Nos. 5,275,796 and 5,395,805.
[0077] A preferred embodiment of extracting the liquid phase from the wet gel using supercritical carbon dioxide comprises, for example: first substantially exchanging the first solvent present in the pore network of the gel with liquid carbon dioxide; then heating the wet gel (usually in an autoclave) above the critical temperature of carbon dioxide (about 31.06° C.) and increasing the system pressure to a pressure greater than the critical pressure of carbon dioxide (about 1070 psig). The pressure surrounding the gel material may be slightly varied to facilitate the removal of the supercritical carbon dioxide from the gel. The carbon dioxide may be circulated through the extraction system to facilitate the continued removal of the first solvent from the wet gel. Finally, the temperature and pressure are slowly returned to ambient conditions to produce a dry aerogel material. The carbon dioxide may also be pre-processed to a supercritical state before being injected into the extraction chamber.
[0078] An example of an alternative method for forming aerogels includes acidifying an alkaline metal oxide precursor (such as sodium silicate) in water to produce a hydrogel. Salt byproducts can be removed from the silicate precursor by ion exchange and / or washing the subsequently formed gel with water. Removal of water from the pores of the gel can be performed by exchange with a polar organic solvent such as ethanol, methanol, or acetone. The liquid phase in the gel is then at least partially extracted using innovative processing and extraction techniques.
[0079] Another example of an alternative method for forming aerogels includes reducing the deleterious capillary pressure at the solvent / pore interface by chemically modifying the matrix material in a wet hydrogel state by converting surface hydroxyl groups to hydrophobic trimethylsilyl ethers, thereby allowing the liquid phase to be extracted from the gel material at a temperature and pressure below the critical point of the solvent.
[0080] Large-scale production of aerogel materials or compositions may be complicated by the difficulty associated with continuously forming gel materials on a large scale; and the difficulty associated with extracting a liquid phase from the gel materials in large volumes using innovative processing and extraction techniques. The aerogel materials or compositions of the present invention are preferably suitable for large-scale production. In certain embodiments, the gel materials of the present invention may be mass-produced via a continuous casting and colloidization process. In certain embodiments, large-scale production of the gel materials or compositions of the present invention requires the use of a large-scale extraction vessel. The large-scale extraction vessel of the present invention may include a vessel having a volume of about 0.1 m 3 or larger, about 0.25m 3 or larger, about 0.5m 3 or larger, or about 0.75m 3 Or larger extraction vessels.
[0081] The gel composition of the present invention may have a thickness of 15 mm or less, 10 mm or less, 5 mm or less, 3 mm or less, 2 mm or less, or 1 mm or less.
[0082] The dried aerogel material or composition may be further processed to optimize target properties of the aerogel material or composition. In certain embodiments, the dried aerogel composition may be subjected to one or more thermal treatments, such as pyrolysis, to produce a thermally treated aerogel composition. Carefully controlled thermal treatments may be used to reduce or stabilize the hydrocarbon fuel content of the aerogel material or composition, which may improve the corresponding HOC and T of the aerogel material or composition. d Properties. In certain embodiments, thermal treatment of the dry aerogel composition can occur under a range of temperatures, pressures, durations, and atmospheric conditions.
[0083] In certain embodiments of the present invention, a treatment temperature of 200° C. or more, 250° C. or more, 300° C. or more, 350° C. or more, 400° C. or more, 450° C. or more, 500° C. or more, 550° C. or more, 600° C. or more, 650° C. or more, 700° C. or more, 750° C. or more, 800° C. or more, or a range between any two of the values may be applied to the dry aerogel composition.
[0084] In certain embodiments of the present invention, the dry aerogel composition may be applied for 3 hours or more, between 10 seconds and 3 hours, between 10 seconds and 2 hours, between 10 seconds and 1 hour, between 10 seconds and 45 minutes, between 10 seconds and 30 minutes, between 10 seconds and 15 minutes, between 10 seconds and 5 minutes, between 10 seconds and 1 minute, between 1 minute and 3 hours, between 1 minute and 1 hour, between 1 minute and 45 minutes, between 1 minute and 30 minutes, between 1 minute and 15 minutes, between 1 minute and 5 minutes, between 10 seconds and 1 minute, between 1 minute and 3 hours, between 1 minute and 1 hour, between 1 minute and 45 minutes, between 1 minute and 30 minutes, between 1 minute and 15 minutes, between 1 minute and 5 minutes, between 10 seconds and 1 minute. One or more heat treatments of between 1 minute and 3 hours, 10 minutes and 1 hour, 10 minutes and 45 minutes, 10 minutes and 30 minutes, 10 minutes and 15 minutes, 30 minutes and 3 hours, 30 minutes and 1 hour, 30 minutes and 45 minutes, 45 minutes and 3 hours, 45 minutes and 90 minutes, 45 minutes and 60 minutes, 1 hour and 3 hours, 1 hour and 2 hours, or 1 hour and 90 minutes, or a range between any two of the values.
[0085] In certain embodiments of the present invention, a treatment temperature of 200° C. to 750° C. may be applied to the dry aerogel composition for 10 seconds to 3 hours.
[0086] Thermal treatment of the aerogel material or composition may occur in a reduced oxygen environment. In the context of the present invention, the term "reduced oxygen environment" refers to an atmosphere comprising a volume concentration of 10 vol% oxygen or less (which is less than the amount of oxygen in ambient air at standard conditions). A reduced oxygen environment may include a positively pressurized atmosphere with an increased concentration of an inert gas (including but not limited to nitrogen, argon, helium, neon, argon, and xenon). A reduced oxygen environment may also include a vacuum atmosphere with a reduced oxygen concentration, including vacuum and partial vacuum. A reduced oxygen environment may further include an atmosphere contained in a sealed container in which limited combustion has consumed a portion of the oxygen content in the sealed atmosphere. A reduced oxygen environment may include 10 vol% oxygen or less, 8 vol% oxygen or less, 6 vol% oxygen or less, 5 vol% oxygen or less, 4 vol% oxygen or less, 3 vol% oxygen or less, 2 vol% oxygen or less, or 1 vol% oxygen or less. The reduced oxygen environment may include between 0.1 and 10 vol% oxygen, between 0.1 and 5 vol% oxygen, between 0.1 and 3 vol% oxygen, between 0.1 and 2 vol% oxygen, or between 0.1 and 1 vol% oxygen. In one embodiment of the present invention, the hydrophobic aerogel material or composition is heat treated in a reduced oxygen atmosphere including between about 85% and about 99.9% inert gas (such as nitrogen). In a preferred embodiment of the present invention, the dry hydrophobic aerogel composition is heat treated in a reduced oxygen atmosphere including between about 95% and about 99.9% inert gas (such as nitrogen) for between about 1 minute and about 3 hours.
[0087] Thermal treatment of aerogel materials or compositions can be highly determinative of various properties of certain aerogel materials. For example, Rao et al. (J. Sol-Gel Sci. Tech., 2004, 30: 141-147) teach an aerogel material made from a TEOS precursor and a variety of hydrophobic agents (including MTMS, MTES, TMES, PhTES, ETES, DMCS, TMCS and HMDZ) added via both co-gelation and surface derivatization to provide hydrophobicity, but all lose their hydrophobicity when exposed to temperatures above 310°C (except for DMCS co-gel, which is stable up to 390°C, and PhTES co-gel, which is stable up to 520°C); Liu et al. (J. Sol-Gel Sci. Tech., 2004, 30: 141-147) teach an aerogel material made from a TEOS precursor and a variety of hydrophobic agents (including MTMS, MTES, TMES, PhTES, ETES, DMCS, TMCS and HMDZ) added via both co-gelation and surface derivatization to provide hydrophobicity; all lose their hydrophobicity when exposed to temperatures above 310°C (except for DMCS co-gel, which is stable up to 390°C, and PhTES co-gel, which is stable up to 520°C); Liu et al. (J. Sol-Gel Sci. Tech., 2012, 62: 126-133) teaches an aerogel material made from a sodium silicate precursor, which is treated with HMDZ to provide hydrophobicity, but loses its hydrophobicity when exposed to a temperature above 430°C in a standard atmosphere; Zhou et al. (Inorg. Mat., 2008, 44-9: 976-979) teaches an aerogel material made from a TEOS precursor, which is treated with TMCS to provide hydrophobicity, but loses its hydrophobicity when exposed to a temperature above 500°C in a standard atmosphere. In one embodiment, the heat treatment of the aerogel material or composition of the present invention is limited to a temperature exposure below 950°C, below 900°C, below 850°C, below 800°C, below 750°C, below 700°C, below 650°C, or below 600°C.
[0088] In certain embodiments, the present invention provides aerogel materials, compositions and processing methods that can be thermally treated to reduce or stabilize the hydrocarbon fuel content of the aerogel material (thereby improving the corresponding properties of the aerogel material such as HOC and T d ); and it can also enable the aerogel material to maintain a functional degree of hydrophobicity at high temperatures, including exposure to temperatures of about 550°C or higher, and exposure to temperatures of about 650°C or higher.
[0089] Embodiments of the present invention may be implemented using any of the processing, extraction and treatment techniques described herein, as well as other processing, extraction and treatment techniques known in the art, to produce aerogels, aerogel-like materials, and aerogel compositions as defined herein.
[0090] Aerogel compositions can be fiber reinforced with various fiber reinforcements to achieve a more flexible, resilient, and conformable composite product. The fiber reinforcements can be added to the gel at any point in the gelation process to produce a wet, fibrous gel composition. The wet gel composition can then be dried to produce a fiber reinforced aerogel composition. The fiber reinforcements can be in the form of discrete fibers, woven materials, nonwoven materials, batting, mesh fabrics, mats, and felt products. The fiber reinforcements can be made of organic fiber materials, inorganic fiber materials, or a combination thereof.
[0091] In a preferred embodiment, the non-woven fiber reinforcement material is incorporated into the aerogel composition as a continuous sheet of interconnected or interwoven fiber reinforcement material. The process includes initially producing a continuous sheet of fiber reinforced gel by casting or pouring a gel precursor solution into a continuous sheet of interconnected or interwoven fiber reinforcement material. The liquid phase may then be at least partially extracted from the fiber reinforced gel sheet to produce a sheet-like, fiber reinforced aerogel composition.
[0092] The aerogel composition may also include a sunscreen to reduce the radiative component of thermal transfer. A sunscreen compound or a precursor thereof may be dispersed into the mixture including the gel precursor at any point prior to gel formation. Examples of sunscreen compounds include, but are not limited to: boron carbide [B4C], diatomaceous earth, manganese ferrite, MnO, NiO, SnO, Ag2O, Bi2O3, carbon black, titanium oxide, iron titanium oxide, aluminum oxide, zirconium silicate, zirconium oxide, iron (II) oxide, iron (III) oxide, manganese dioxide, iron titanium oxide (ilmenite), chromium oxide, carbide (such as SiC, TiC or WC), or mixtures thereof. Examples of sunscreen compound precursors include, but are not limited to: TiOSO4 or TiOCl2.
[0093] The aerogel materials and compositions of the present invention have been shown to be highly effective as insulating materials. However, the application of the methods and materials of the present invention is not intended to be limited to insulation-related applications. The methods and materials of the present invention can be applied to any system or application that can benefit from the unique combination of properties or procedures provided by the materials and methods of the present invention.
[0094] The following examples provide various non-limiting embodiments and properties of the present invention.
[0095] Example 1-
[0096] K grade sodium silicate was used as a precursor, which includes 2.88 weight ratios of SiO2:Na2O and contains 31.7 wt% SiO2 and 11 wt% Na2O. Sodium methylsiliconate was obtained from 30% NaSiO3CH3 in water. The sodium silicate and sodium methylsiliconate were combined so that 31.4% of the resulting aerogel mass was derived from sodium methylsiliconate (SiO2 from NaSiO3CH3). 1.5CH3), with an expected hydrophobic organic content of 7.0 wt% within the aerogel material.
[0097] This combination was diluted with water before adding it to 32% H2SO4 to give 9.68 wt% silica solids (6.64 wt% SiO2 and 3.04 wt% SiO 1.5 CH3). Both H2SO4 and Na2SiO3 are cooled to 10°C in an ice bath. Na2SiO3 is slowly added to H2SO4 with rapid stirring. This exothermic addition is performed at a rate such that the temperature never exceeds 12°C to avoid gelation. The sol is cooled to 4°C to induce some precipitation of Na2SO4.10H2O. The temperature of the solution is maintained at 4°C. To further precipitate sodium sulfate, ethanol is added in an amount equivalent to 68.7% by volume of the aqueous sol, so that the molar ratio of the components in the sol is 1:0.409:2.34:6.97:0.156 Si (from water glass):Si (from methylsiliconate):EtOH:H2O:H2SO4. The Na2SO4 is immediately removed by vacuum filtration.
[0098] The gel was cast at a target aerogel density of 0.07-0.08 g / cc by adding dilute ammonium hydroxide as a catalyst (10 vol% of 28% NH4OH in water). 85 vol% sol, 5 vol% EtOH, and 10 vol% catalyst flow (added over a few seconds) were used. After catalyst addition, the sol was stirred at 300 rpm for 30 seconds and then cast into a fiber reinforcement phase and gelled. After curing for about 1 hour, the aerogel material was placed in an EtOH bath at a 3:1 EtOH:gel volume ratio for 6 hours to reduce the water content before aging. It was then aged at 68°C for 14 hours in an ethanol aging fluid containing 0.8 wt / vol% NH3 at a 3:1 fluid:gel ratio. The sample was subjected to solvent extraction with supercritical CO2 and then dried at 110°C for 2 hours.
[0099] The fiber reinforcement phase was silica PD batt with 9 micron diameter fibers, about 10 mm thick and a density of about 3.8 oz / sq ft. The resulting aerogel material was about 45 wt% aerogel and 55 wt% fiber, resulting in an expected material density of about 0.16-0.20 g / cc (yielding 0.07-0.08 g / cc aerogel density).
[0100] Example 2-
[0101] The sol was made by co-hydrolyzing TEOH and MTES in EtOH and H2O with an acid catalyst. The molar ratio of the sol material was adjusted to obtain an aerogel with about 7.0 wt% organic content in the aerogel material. The sol was stirred at 60°C for 4 hours and then cooled to room temperature. There was about 3% sol volume loss during the hydrolysis, and EtOH was added to return the sol to its original volume.
[0102] 0.5M NH4OH was added to the combined sol with a target aerogel density of 0.07-0.08 g / cc. The sol was cast into a fiber reinforcement phase and gelled. After curing for about 1 hour, the aerogel material was aged at 68°C for about 16 hours in an ethanol aging fluid containing 0.8 wt / vol% NH3 at a fluid:gel ratio of 3:1. The sample was subjected to solvent extraction with supercritical CO2 and then dried at 110°C for 2 hours.
[0103] The fiber reinforcement phase was silica PD batt with 9 micron diameter fibers, about 10 mm thick and a density of about 3.8 oz / sq ft. The resulting aerogel material was about 45 wt% aerogel and 55 wt% fiber, resulting in an expected material density of about 0.16-0.20 g / cc (yielding 0.07-0.08 g / cc aerogel density).
[0104] Example 3-
[0105] The sol was made by co-hydrolyzing TEOH and MTES in EtOH and H2O with an acid catalyst. The molar ratio of the sol material was adjusted to obtain an aerogel having an organic content of about 7.0 wt% in the aerogel material. The sol was stirred at 60°C for 4 hours and then cooled to room temperature. Boron carbide [B4C], carbon black, manganese dioxide, titanium oxide, or zirconium silicate was incorporated into the combined sol in batches, which were then stirred for not less than 1 hour.
[0106] 0.5M NH4OH was added to the combined sol with a target aerogel density of 0.07-0.08 g / cc. The sol was cast into a fiber reinforcement phase and gelled. After curing for about 1 hour, the aerogel material was aged at 68°C for about 16 hours in an ethanol aging fluid containing 0.8 wt / vol% NH3 at a fluid:gel ratio of 3:1. The sample was subjected to solvent extraction with supercritical CO2 and then dried at 110°C for 2 hours.
[0107] The fiber reinforcement phase was silica PD batt with 9 micron diameter fibers, about 10 mm thick and a density of about 3.8 oz / sq ft. The resulting aerogel material was about 45 wt% aerogel and 55 wt% fiber, resulting in an expected material density of about 0.16-0.20 g / cc (yielding 0.07-0.08 g / cc aerogel density).
[0108] Example 4-
[0109] A polyethyl silicate sol is made by hydrolyzing TEOS in EtOH and H2O with an acid catalyst, followed by stirring at room temperature for not less than 6 hours. A polymethylsilsesquioxane sol is made by hydrolyzing MTES in EtOH and H2O with an acid catalyst, followed by stirring at room temperature for not less than 6 hours. Polyethyl silicate (TEOS) and polymethylsilsesquioxane (MTES) are combined to obtain an aerogel having an organic content of about 10-11 wt%. Silicon carbide powder (F1200 Grit) or titanium dioxide powder is incorporated into the combined sol in batches, with a sol-to-powder weight ratio of about 15:1. The combined sol is stirred for not less than 1 hour.
[0110] 0.5M NH4OH was added to the combined sols with a target aerogel density of 0.07-0.08 g / cc. The sol was cast into a non-woven, glass fiber reinforced phase and gelled. The aerogel material was aged in an ethanol aging fluid containing 0.5 wt / vol% NH3 for no less than 10 hours. The sample was subjected to solvent extraction with supercritical CO2 and then dried with conventional heat at about 180°C.
[0111] The resulting aerogel material was approximately 45 wt% aerogel and 55 wt% fiber, resulting in an expected material density of approximately 0.16-0.20 g / cc (yielding 0.07-0.08 g / cc aerogel density).
[0112] Example 5-
[0113] A polyethyl silicate sol is prepared by hydrolyzing TEOS in EtOH and H2O with an acid catalyst, followed by stirring at room temperature for not less than 6 hours. A polymethylsilsesquioxane sol is prepared by hydrolyzing MTES in EtOH and H2O with an acid catalyst, followed by stirring at room temperature for not less than 6 hours. Polyethyl silicate (TEOS) and polymethylsilsesquioxane (MTES) are combined to obtain an aerogel having an organic content of about 10-11 wt%. Iron oxide, titanium carbide, diatomaceous earth, manganese ferrite or iron titanium dioxide are incorporated into the combined sol in batches. The combined sol is stirred for not less than 1 hour.
[0114] 0.5M NH4OH was added to the combined sol with a target aerogel density of 0.07-0.08 g / cc. The sol was cast into a non-woven, glass fiber reinforced phase and gelled. The aerogel material was aged in an ethanol aging fluid containing 0.5 wt / vol% NH3 for no less than 10 hours. The sample was subjected to solvent extraction with supercritical CO2 and then dried with conventional heat at about 180°C.
[0115] The resulting aerogel material was approximately 45 wt% aerogel and 55 wt% fiber, resulting in an expected material density of approximately 0.16-0.20 g / cc (yielding 0.07-0.08 g / cc aerogel density).
[0116] Example 6-
[0117] The sol was prepared by co-hydrolyzing TEOS and an organosilane hydrophobe in EtOH and 1 mM aq oxalic acid. The organosilane hydrophobe co-precursor may be selected from the following: methyltrimethoxysilane (MTMS), methyltriethoxysilane (MTES), trimethylethoxysilane (TMES), ethyltriethoxysilane (ETES), and phenyltriethoxysilane (PhTES). In this example, PhTES was used as the organosilane hydrophobe. The molar ratio of EtOH:H2O:oxalic acid was kept constant at 5:7:1.26x10 -4 , oxalic acid and water were introduced together at 1 mM oxalic acid. The molar ratios of TEOS and PhTES were provided to obtain aerogels with 8.0 and 9.0 wt% hydrophobic organic content in each case and a target density of 0.07-0.08 g / cc. The molar ratios of the sol components of the two formulations were 0.0719:1:8.98:12.57:2.26x10 -4 and 0.0825:1:9.18:12.85:2.3x10 -4 PhTES:TEOS:EtOH:H2O:oxalic acid.
[0118] The sol was stirred for 15 minutes and then cast into a fiber reinforcement phase and gelled in an oven at 60°C. After curing at 60°C for 21-33 hours, the aerogel material was aged at 68°C for 22 hours in an ethanol aging fluid containing 0.8 wt / vol% NH3 at a fluid:gel ratio of 3:1. The sample was subjected to solvent extraction with supercritical CO2 and then dried at 110°C for 2 hours.
[0119] The fiber reinforcement phase was silica PD batt with 9 micron diameter fibers, about 10 mm thick and a density of about 3.8 oz / sq ft. The resulting aerogel material was about 45 wt% aerogel and 55 wt% fiber, resulting in an expected material density of about 0.16-0.20 g / cc (yielding 0.07-0.08 g / cc aerogel density).
[0120] Example 7-
[0121] The sol was prepared by co-hydrolysis of TEOS and PhTES in MeOH with 1 mM aq oxalic acid catalyst. The molar ratio of MeOH:H2O:oxalic acid was kept constant at 66:7:1.26x10 -4, oxalic acid was introduced with water at 1 mM oxalic acid. The target density for all formulations was 0.07-0.08 g / cc. The PhTES content was varied to achieve aerogels with a target organic content of 7.0, 11.0, or 19.0 wt%. The molar ratios of the sol components for these formulations were 1:0.062:16.57:1.76:3.16x10 -5 ,1:0.105:18.15:1.93:3.47x10 -5 , and 1: 0.217: 22.18: 2.35: 4.24x10 -5 TEOS:PhTES:MeOH:H2O:oxalic acid The sol was stirred at 28°C for 24 hours.
[0122] To gel the hydrolyzed sol, 1M NH4OH was added at an additional 1 mol of HO per mol of HO added in the previous step. This resulted in 0.0316, 0.0347, or 0.0424 mol of NH4OH per mol of TEOS for the 7.0, 11.0, and 19.0 wt% organic formulations, respectively. The sol was stirred for 3 minutes, then cast into a fiber reinforcement phase and allowed to gel at 28°C. The gel was allowed to cure at room temperature for 2 days, then soaked in an ethanol bath with fresh ethanol every 24 hours for 4 days. The samples were subjected to solvent extraction with supercritical CO2 and then dried at 110°C for 2 hours.
[0123] The fiber reinforcement phase was silica PD batt with 9 micron diameter fibers, about 10 mm thick and a density of about 3.8 oz / sq ft. The resulting aerogel material was about 45 wt% aerogel and 55 wt% fiber, resulting in an expected material density of about 0.16-0.20 g / cc (yielding 0.07-0.08 g / cc aerogel density).
[0124] Example 8-
[0125] The sol was prepared by co-hydrolyzing tetramethyl orthosilicate (TMOS) and PhTES in MeOH with 86 mM NH4OH catalyst. The molar ratio between solvent and catalyst was kept constant at 11:5:3.7x10 -3 MeOH:H2O:NH4OH, NH4OH and water were introduced together with 86mM NH4OH. The final density of all formulations was 0.07-0.08g / cc. The PhTES content was varied to achieve aerogels with a target organic content of 7.0, 11.0, or 19.0wt%. The molar ratios of the sol components of these formulations were 1:0.062:16.61:7.55:5.59x10 -3 ,1:0.105:18.04:8.20:6.07x10 -3, and 1: 0.217: 21.78: 9.90: 7.33x10 -3 TMOS: PhTES: MeOH: H2O: NH4OH.
[0126] The sol was stirred for 15 minutes, then cast into a fiber reinforcement phase and gelled. The gel was cured at room temperature for 3 days and then soaked in an ethanol bath for 4 days with fresh ethanol every 24 hours. The sample was subjected to solvent extraction with supercritical CO2 and then dried at 110°C for 2 hours.
[0127] The fiber reinforcement phase was silica PD batt with 9 micron diameter fibers, about 10 mm thick and a density of about 3.8 oz / sq ft. The resulting aerogel material was about 45 wt% aerogel and 55 wt% fiber, resulting in an expected material density of about 0.16-0.20 g / cc (yielding 0.07-0.08 g / cc aerogel density).
[0128] Example 9-
[0129] The sol was prepared by co-hydrolyzing TEOS and 1,2-bis(triethoxysilyl)ethane (BTESE) in EtOH and water using 1 M HCl catalyst. -3 ,1:0.275:15.04:3.76:2.63x10 -3 , and 1: 0.334: 16.24: 4.06: 2.84x10 -3 Aerogels with 7.0, 8.0, or 9.0 wt% organic content were obtained by adjusting the molar ratio of TEOS:BTESE:EtOH:H2O:HCl. In each case, the ratio between solvent and catalyst was kept constant at 8:2:1.4x10 -3 EtOH:H2O:HCl while varying the BTESE content. The sol was stirred at 60°C for 4 hours and then cooled to room temperature. There was a loss of about 3% sol volume during the hydrolysis and EtOH was added to return the sol to its original volume.
[0130] To gel the hydrolyzed sol, dilute NH4OH was added so that the final cast sol contained 8.0 vol% 0.5M NH4OH and the target density of the final aerogel was 0.07-0.08 g / cc. The sol was cast into a fiber reinforcement phase and gelled. After curing for about 1 hour, the aerogel material was aged at 68°C for about 16 hours in an ethanol aging fluid containing 0.8 wt / vol% NH3 at a fluid:gel ratio of 3:1. The sample was subjected to solvent extraction with supercritical CO2 and then dried at 110°C for 2 hours.
[0131] The fiber reinforcement phase was silica PD batting with 9 micron diameter fibers, about 10 mm thick and a density of about 3.8 oz / sq ft. The resulting aerogel material was about 45 wt% aerogel and 55 wt% fiber, giving an expected material density of about 0.16-0.20 g / cc (yielding 0.07-0.08 g / cc aerogel density).
[0132] Example 10-
[0133] K grade sodium silicate was used as the precursor, which consisted of 2.88 weight ratios of SiO2:Na2O and contained 31.7wt% SiO2 and 11wt% Na2O. The sodium silicate precursor was first diluted with water and then added to 32% H2SO4. The resulting solution contained 10.34wt% SiO2, 1.34M Na + , and 1.50MH + . Cool both H2SO4 and Na2SiO3 to 10°C in an ice bath. Slowly add Na2SiO3 to H2SO4 with rapid stirring. Do this exothermic addition at a rate that the temperature never exceeds 12°C to avoid gelation. Cool the sol to 4°C to induce some precipitation of Na2SO4.10H2O. Keep the temperature of the solution at 4°C.
[0134] THF is added in an amount until there is 6.72 wt% SiO2 in the final sol, thereby further precipitating Na2SiO4. Na2SO4 is immediately removed by vacuum filtration, and NaCl is added to the filtered sol solution until the sol is saturated. NaCl triggers the separation of the aqueous phase from the organic phase. 95% H2O is removed from the organic phase, and 100% SiO2 is layered into the organic phase. The organic phase is isolated, with an expected solid content of about 0.18 g SiO2 / mL. Ethanol is added in an amount equivalent to 104% by volume of the THF layer, so that the molar ratio of the components in the sol is 1 (Si): 6.256 (EtOH): 0.975 (H2O): 4.115 (THF).
[0135] An MTES precursor sol solution was prepared, comprising: 69.4 wt % MTES with 2.7 H2O:Si (molar ratio) and 70 mM acetic acid (99.7%) diluted in EtOH, which provided an expected 26 wt % solid content [SiO 1.5 (CH3)]. The molar ratio of MTES:EtOH:H2O:HOAc was 1:0.624:2.703:0.0199. The sol was stirred in a thermos for 5 hours and then quenched by cooling.
[0136] 85.9 vol% silicate sol (1a) and 14.1 vol% MTES sol (1b) were combined and stirred for another 2 hours. 1.5 CH3) with an expected final aerogel mass of 31.4 wt% and an expected hydrophobic organic content of 7.0 wt%.
[0137] The gel was cast at a target aerogel density of 0.07-0.08 g / cc by adding EtOH and dilute ammonium hydroxide as a catalyst (2.5 vol% of 28% NH4OH in water). A 67 vol% sol solution, 21 vol% EtOH, and a 12 vol% catalyst stream (added over a few seconds) were used. After catalyst addition, the sol was stirred at 300 rpm for 30 seconds and then cast into a fiber reinforcement phase and gelled. After curing for about 1 hour, the aerogel material was aged at 68°C for about 16 hours in an ethanol aging fluid containing 0.8 wt / vol% NH3 at a fluid:gel ratio of 3:1. The samples were subjected to solvent extraction with supercritical CO2 and then dried at 110°C for 2 hours.
[0138] The fiber reinforcement phase was silica PD batt with 9 micron diameter fibers, about 10 mm thick and a density of about 3.8 oz / sq ft. The resulting aerogel material was about 45 wt% aerogel and 55 wt% fiber, resulting in an expected material density of about 0.16-0.20 g / cc (yielding 0.07-0.08 g / cc aerogel density).
[0139] Example 11-
[0140] K grade sodium silicate was used as the precursor, which has a SiO2:Na2O ratio of 2.88 by weight, contains 31.7wt% SiO2 and 11wt% Na2O, and has a density of 1.48g / mL. It was first diluted with water so that the diluted solution contained 22.1wt% of the original water glass (7.0wt% SiO2). + The diluted sodium silicate was ion exchanged with a resin. The resulting silicic acid was then gelled by adding H2O and 1M NH4OH catalysts so that the diluent H2O and catalyst streams constituted 6.9 vol% and 0.4 vol% of the final hydrosol, respectively. The sol was stirred at 300 rpm for 30 seconds before casting into the fiber reinforcement phase and gelling. The molar ratio of Si:H2O:NH3 was 1:47.8:0.0016 and the target silica aerogel density was 0.07-0.08 g / cc. The gel was aged at 50°C for 3 hours. Solvent exchange was performed three times with ethanol over 36 hours, followed by three exchanges of ethanol with hexane over 36 hours.
[0141] The fiber reinforcement phase was silica PD batting with 9 micron diameter fibers, about 10 mm thick, and a density of about 3.8 oz / sq ft. The resulting aerogel material was about 45 wt% aerogel and 55 wt% fiber, resulting in an expected material density of about 0.16-0.20 g / cc (yielding 0.07-0.08 g / cc aerogel density without hydrophobic treatment).
[0142] The wet gel was hydrophobized with one of the following hydrophobic silylating agents: methyltrimethoxysilane (MTMS), methyltriethoxysilane (MTES), vinyltrimethoxysilane (VTMS), phenyltrimethoxysilane (PhTMS), phenyltriethoxysilane (PhTES), or dimethyldimethoxysilane (DMDMS). Silanization of the gel was performed in a hexane bath containing 20 vol% hydrophobe at 50°C for 24 hours using a fluid:gel ratio of 4:1. The molar ratio of hydrophobe in the fluid to Si in the gel was 2.8-5.0, depending on which hydrophobe was used. The gel was rinsed twice with hexane for 24 hours, then solvent extraction was applied with supercritical CO2, and then dried at 110°C for 2 hours.
[0143] Example 12-
[0144] The silica gel was prepared by hydrolysis and condensation of TEOS diluted with EtOH in the presence of oxalic acid catalyst. The molar ratio of TEOS:EtOH:H2O:oxalic acid was 1:7.60:10.64:1.92x10 -4 , oxalic acid was introduced with water at 1 mM oxalic acid. The target silica aerogel density was 0.07-0.08 g / cc aerogel. The sol was stirred for 15 minutes, then cast into a fiber reinforcement phase and gelled in an oven at 60°C.
[0145] The fiber reinforcement phase was silica PD batting with 9 micron diameter fibers, about 10 mm thick, and a density of about 3.8 oz / sq ft. The resulting aerogel material was about 45 wt% aerogel and 55 wt% fiber, resulting in an expected material density of about 0.16-0.20 g / cc (yielding 0.07-0.08 g / cc aerogel density without hydrophobic treatment).
[0146] The gel was transferred to a bath containing 20 vol% hydrophobic agent in methanol using a 4:1 fluid:gel ratio and heated at 45°C for 24 hours. The hydrophobic agent was one of the following: methyltrimethoxysilane (MTMS), methyltriethoxysilane (MTES), ethyltriethoxysilane (ETES), or phenyltriethoxysilane (PhTES). The molar ratio of hydrophobe in the fluid to Si in the gel was 2.8-4.8, depending on which hydrophobe was used. The gel was rinsed three times with EtOH at 45°C for 6 hours each, then solvent extraction was applied with supercritical CO2, and then dried at 110°C for 2 hours.
[0147] Example 13-
[0148] Examples 1, 2, 6, 7, 8 and 9 produced aerogel compositions having a hydrophobic organic content of about 7.0-9.0 wt% in the aerogel material (3.0-5.0 wt% of the composite) as expected in each example. Example 4 produced an aerogel composition having a hydrophobic organic content of about 9.0-11.0 wt% in the aerogel material (4.0-6.0 wt% of the composite). Examples 7 and 8 also produced aerogel compositions having a hydrophobic organic content of about 11.0 wt% and 19.0 wt% PhTES in the aerogel material (6.0-9.0 wt% of the composite). Examples 3 and 5 can produce aerogel compositions having a hydrophobic organic content of about 9.0-11.0 wt% in the aerogel material by adjusting the manufacturing conditions (amount of hydrophobic material, time, temperature, etc.). In Examples 10-12, by adjusting the manufacturing conditions (the amount of hydrophobic material, time, temperature, etc.), an aerogel composition having a hydrophobic organic content of about 7.0-9.0 wt % in the aerogel material can be prepared.
[0149] The samples prepared in Examples 1, 2, 6, 7, 8 and 9, and the sample prepared in Example 4 including silicon carbide powder, were heat treated in a tube furnace under N2 at a temperature ramp rate of 10°C / min until the selected treatment temperature reached 200°C to 700°C. After the treatment period was completed, the tube furnace was cooled to room temperature before removing the sample.
[0150] The samples treated included: 7% MTES sample of Example 2; 7% NaSiO3CH3 sample of Example 1; 7%, 8% and 9% BTESE samples of Example 9; 8% and 9% PhTES samples of Example 6; 7%, 11% and 19% PhTES samples of Example 7; 7%, 11% and 19% PhTES samples of Example 8. Heat treatment was applied to the samples at various temperatures ranging from 200°C to 700°C for 10 seconds to 1 hour. Samples treated at 475°C for 10 minutes and at 525°C for 10 minutes were selected for further testing.
[0151] The samples prepared in Example 4 including titanium dioxide powder were heat treated for no longer than 60 minutes by sealing each batch of samples in stainless steel foil bags and placing the foil bags in an inert furnace preheated at various temperatures between 450° C. and 800° C. The treated samples of Example 4 are identified in the present invention by powder material (S=silicon carbide; T=titanium dioxide), heat treatment temperature (450-800° C.) and treatment time (0-60).
[0152] Thermal treatment of the 7%, 8% and 9% BTESE samples showed signs of decomposition starting at about 475° C. Thermal treatment of the PhTES samples all showed signs of unstable phenyl species at elevated temperatures above 400° C.
[0153] Example 14-
[0154] Table 1 shows the density measurements of the treated aerogel composite samples of Example 13. Density measurements were performed in accordance with ASTM C 167. All composite aerogel samples had a measured density below 0.216 g / cc.
[0155] Example 15-
[0156] Table 1 shows the thermal conductivity (TC) measurements of the treated aerogel composite samples of Example 13. TC measurements were performed according to ASTM C177 at a temperature of about 37.5°C and a compression of 2 psi (8x8 samples) or 8 psi (4x4 samples).
[0157] All processed aerogel composite samples measured thermal conductivity values at or below 31.6 mW / mK.
[0158] Example 16-
[0159] Aerogel compositions having a hydrophobic organic content of about 7.0-8.0 wt% are generally expected to be hydrophilic when prepared, with expected C1511 water absorption values (15 minutes immersion under ambient conditions) of about 350 wt% or more.
[0160] Table 1 shows the water absorption measurements of the treated aerogel composite samples both before and after the reduced oxygen heat treatment of Example 13. All measurements were performed in accordance with ASTM C1511 (15 minutes immersion under ambient conditions).
[0161] The 7% MTES and 7% NaSiO3CH3 pre-treated samples both had water absorption measurements greater than 400 wt% water absorption. The 7%, 8% and 9% BTESE pre-treated samples all had water absorption measurements greater than 340 wt% water absorption. The PhTES material pre-treated samples all had water absorption measurements greater than 280 wt%.
[0162] The 7% MTES post-treated samples had a water absorption measurement of about 0.0 wt% water absorption, which is lower than the 7% MTES pre-treated samples. The 7% NaSiO3CH3 post-treated samples had a water absorption measurement of about 81% water absorption (samples heat treated at 475°C for 10 minutes). All BTESE post-treated samples had a water absorption measurement of greater than 290 wt% water absorption. All PhTES post-treated samples had a water absorption measurement of greater than 275 wt% water absorption.
[0163] Example 17-
[0164] Table 1 shows the heat of combustion (HOC) measurements of the treated aerogel composite samples both before and after the reduced oxygen heat treatment of Example 13. The HOC measurements were performed according to conditions comparable to the ISO 1716 measurement standard.
[0165] The pre-treated sample of 7% MTES had a HOC measurement of about 600 cal / g; the post-treated sample (heat treated at 525°C for 10 minutes) had a HOC measurement of about 425 cal / g. The pre-treated sample of 7% NaSiO3CH3 had a HOC measurement of about 415 cal / g; the post-treated sample (heat treated at 525°C for 10 minutes) had a HOC measurement of about 140 cal / g. The pre-treated sample of 9% BTESE had a HOC measurement of about 780 cal / g; the post-treated sample of 9% BTESE (heat treated at 525°C for 10 minutes) had a HOC measurement of about 285 cal / g. The pre-treated sample of 9 wt% PhTES (from Example 3-1) had a HOC measurement of about 437 cal / g; the post-treated sample (heat treated at 525°C for 10 minutes) had a HOC measurement of about 144 cal / g. The pre-treated sample of 7 wt% PhTES (from Example 3-3) had a HOC measurement of about 351 cal / g; the post-treated sample (heat treated at 400°C for 10 minutes) had a HOC measurement of about 120 cal / g. The pre-treated sample of 11 wt% PhTES (from Example 3-3) had a HOC measurement of about 403 cal / g; the post-treated sample (heat treated at 400°C for 10 minutes) had a HOC measurement of about 110 cal / g.
[0166] Example 18-
[0167] Figure 1 The CP / MAS of the 7% MTES sample of Example 13 before and after the oxygen reduction heat treatment at 525°C for 10 minutes is shown. 29 Si solid state NMR analysis.
[0168] The 7% MTES pre-treated sample showed a T of about 0.463 1-2 :T3 ratio, and a Q of about 1.961 2-3 :Q 4 The 7% MTES post-treatment sample showed a T of about 0.272. 1-2 :T 3 ratio, and a Q of about 0.842 2-3 :Q 4 Ratio. Overlapping peaks are individually decompressed and integrated to obtain a ratio.
[0169] Embodiment 19
[0170] Figure 2 The figure shows the TGA / DSC analysis of the 7% MTES sample, 7% NaSiO3CH3 sample, 9% BTESE sample, and 9% PhTES (from Example 3-1) sample of Example 13 before and after the oxygen reduction heat treatment at 525°C for 10 minutes. The TGA / DSC analysis was performed at a ramp rate of 20°C / min from room temperature to 1000°C.
[0171] Table 1 shows the Figure 2 The TGA / DSC analysis plots shown are the thermal decomposition onset temperatures (° C.) of the post-treated samples.
[0172] The post-treated sample with 7% MTES (heat treated at 525°C for 10 minutes) had a T of about 545°C. d The post-treated sample of 7% NaSiO3CH3 (heat treated at 525°C for 10 minutes) has a T of about 600°C. d The post-treated sample of 9% BTESE (heat treated at 525°C for 10 minutes) has a T of about 460°C. d The post-treated sample of 9% PhTES (heat treated at 525°C for 10 minutes) has a T of about 595°C. d Measurement.
[0173] Table 1
[0174]
[0175] As used herein, the conjunction "and" is intended to be inclusive while the conjunction "or" is not intended to be exclusive, unless otherwise indicated. For example, the phrase "or, or" is intended to be exclusive.
[0176] The terms "a", "an", and other similar terms used in the text describing the present invention (especially in the context of the claims) are to be construed as including both the singular and the plural, unless otherwise indicated or clearly contradicted by context.
[0177] The terms “comprising,” “having,” “including,” and “containing” are to be construed as open-ended terms (ie, meaning “including, but not limited to,”) unless otherwise noted.
[0178] As used herein, "about" refers to the usual degree of deviation from the identified property, composition, amount, value or parameter; for example, based on experimental error, measurement error, approximate error, calculation error, standard deviation from the mean, routine minor adjustments, etc.
[0179] Recitation of ranges of values herein are merely intended to serve as a shorthand method of referring individually to each separate value falling within the range, unless otherwise indicated herein, and each separate value is incorporated into the specification as if it were individually recited herein.
[0180] All methods described herein can be performed in any suitable order, unless otherwise specified in the text or clearly contradictory in the text. Any and all embodiments provided herein, or the use of exemplary language (e.g., "such as", "for example"), are only intended to better illustrate the present invention rather than limit the scope of the present invention, unless otherwise claimed in the scope of the patent.
Claims
1. A method for preparing an aerogel composition, the method comprising: exposing a first silica-based aerogel composition comprising at least one hydrophobically bound silica to a reduced oxygen atmosphere at a temperature greater than 525° C. to one or more thermal treatments, wherein the one or more thermal treatments convert the first silica-based aerogel composition into a second silica-based aerogel composition, The hydrophobic organic material of the second silica-based aerogel composition has a thermal decomposition starting point of the hydrophobic organic material at 500° C. or higher.
2. A method for preparing an aerogel composition, the method comprising: exposing a first silica-based aerogel composition including at least one hydrophobic bonded silica to a reduced oxygen atmosphere at a temperature greater than 525° C. to one or more thermal treatments, wherein the one or more thermal treatments convert the first silica-based aerogel composition into a second silica-based aerogel composition, and The second silica-based aerogel composition has a heat of combustion of less than 750 cal / g.
3. The method according to claim 1 or 2, wherein the second silica-based aerogel composition has a 29 Si NMR analysis determined the T of 0.01 to 0.5 1-2 :T 3 The ratio of species.
4. The method according to claim 1 or 2, wherein the second silica-based aerogel composition has a 29 Q of 0.1 to 1.5 as determined by Si NMR analysis 2-3 :Q 4 The ratio of species.
5. The method of claim 1 or 2, wherein the second silica-based aerogel composition has a nuclear magnetic resonance (NMR) spectrum, comprising using 29 Si NMR analysis determined the T of 0.01 to 0.5 1-2 :T 3 ratio and Q of 0.1 to 1.5 2-3 :Q 4 ratio.
6. The method of claim 1 or 2, wherein the second silica-based aerogel composition has a water absorption rate of 40 wt% or less.
7. The method of claim 1 or 2, wherein the second silica-based aerogel composition has a power consumption of 15 mW / M * K to 40mW / M * K between the thermal conductivity.
8. The method according to claim 1 or 2, wherein the hydrophobic organic content of the second silica-based aerogel composition is between 2 wt% and 15 wt%.
9. The method of claim 1 or 2, wherein the hydrophobic organic material prior to the one or more thermal treatments comprises aliphatic hydrophobic groups; and wherein at least 50% of the hydrophobic organic material comprises the aliphatic hydrophobic groups.
10. The method of claim 1 or 2, wherein the hydrophobic organic material comprises methyl hydrophobic groups; and wherein at least 50% of the hydrophobic organic material comprises the methyl hydrophobic groups.
11. The method of claim 1 or 2, wherein the thermal decomposition onset of the hydrophobic organic material is 525°C to 635°C.
12. The method of claim 1 or 2, wherein the thermal decomposition initiation of the hydrophobic organic material is 550°C to 635°C.
13. The method of claim 1 or 2, wherein the thermal decomposition initiation of the hydrophobic organic material is 600°C to 635°C.
14. The method of claim 1 or 2, wherein the one or more heat treatments in the reduced oxygen atmosphere are performed at a temperature of 700°C or less.
15. The method of claim 1 or 2, wherein the one or more heat treatments in the reduced oxygen atmosphere are performed at one or more temperatures of 525°C to 700°C.
16. The method of claim 1 or 2, wherein the one or more heat treatments in the reduced oxygen atmosphere are performed at one or more temperatures of 525°C to 700°C for at least one minute.
17. The method of claim 1 or 2, wherein the one or more heat treatments in the reduced oxygen atmosphere are performed at one or more temperatures of 525°C to 700°C and for a time of 1 minute to 30 minutes.
18. The method of claim 1 or 2, wherein the one or more thermal treatments in the reduced oxygen atmosphere do not include exposure to a temperature above 700°C for more than 1 minute.
19. The method of claim 1 or 2, wherein the total duration of the one or more heat treatments is between 1 minute and 60 minutes.
20. The method of claim 1 or 2, wherein the total duration of the one or more heat treatments is between 1 minute and 30 minutes.
21. The method of claim 1 or 2, wherein the reduced oxygen atmosphere is 0.01 vol% to 5 vol% oxygen.
22. The method of claim 1 or 2, wherein the reduced oxygen atmosphere is 0.01 vol% to 1 vol% oxygen.
23. The method of claim 1 or 2, wherein the second silica-based aerogel composition further comprises an additive selected from the group consisting of microfibers, fillers, reinforcing agents, stabilizers, thickeners, elastic compounds, opacifiers, coloring or dyeing compounds, radiation absorbing compounds, radiation reflecting compounds, corrosion inhibitors, thermal conductive components, phase change materials, pH adjusters, redox adjusters, HCN moderators, exhaust gas moderators, conductive compounds, dielectric compounds, magnetic compounds, radar blocking components, hardeners, anti-shrinkage agents, smoke suppressants, fire extinguishing agents, and combinations thereof.
24. The method of claim 1 or 2, wherein the second silica-based aerogel composition further comprises an additive, wherein the additive comprises a phase change material.
25. The method of claim 1 or 2, wherein the second silica-based aerogel composition further comprises an additive, wherein the additive comprises a sunscreen.
26. The method of claim 1 or 2, wherein the second silica-based aerogel composition further comprises an additive selected from the group consisting of metal carbides, metal oxides, diatomaceous earth, metal ferrites, and mixtures thereof.
27. The method of claim 1 or 2, wherein the second silica-based aerogel composition further comprises an additive selected from the group consisting of boron carbide, diatomaceous earth, manganese ferrite, MnO, NiO, SnO, Ag2O, Bi2O3, carbon black, titanium oxide, iron titanium oxide, aluminum oxide, zirconium silicate, zirconium oxide, iron (II) oxide, iron (III) oxide, manganese dioxide, iron titanium oxide, chromium oxide, SiC, TiC, WC, and mixtures thereof.
28. The method of claim 1 or 2, wherein the second silica-based aerogel composition further comprises an additive, wherein the additive comprises a carbide selected from the group consisting of boron carbide, silicon carbide, titanium carbide, tungsten carbide, and mixtures thereof.
29. The method of claim 1 or 2, wherein the second silica-based aerogel composition further comprises an additive comprising silicon carbide.
30. The method of claim 1 or 2, wherein the second silica-based aerogel composition further comprises a reinforcement material.
31. The method of claim 30, wherein the reinforcement material comprises a fiber reinforcement material.
32. The method of claim 30, wherein the reinforcement material further comprises a foam reinforcement material.
33. The method of claim 30, wherein the strengthening material comprises boron, aluminum, iron, or carbon.
34. The method of claim 1 or 2, wherein the second silica-based aerogel composition further comprises boron, aluminum, iron or carbon.
35. The method of claim 1 or 2, wherein the second silica-based aerogel composition further comprises aluminum.
36. The method of claim 1 or 2, wherein the second silica-based aerogel composition further comprises steel.
37. The method of claim 1 or 2, wherein the second silica-based aerogel composition comprises boron, aluminum, iron, or carbon.
38. The method of claim 1 or 2, wherein the second silica-based aerogel composition comprises aluminum.
39. The method of claim 1 or 2, wherein the second silica-based aerogel composition comprises at least one of foam, fiber, aluminum, or a combination thereof.
40. The method of claim 2, wherein the heat of combustion is less than 717 cal / g.
41. The method of claim 2, wherein the heat of combustion is from 250 cal / g to 717 cal / g.
42. The method of claim 2, wherein the heat of combustion is from 265 cal / g to 600 cal / g.
43. The method of claim 2, wherein the heat of combustion is from 265 cal / g to 450 cal / g.
44. The method of claim 2, wherein the heat of combustion is from 265 cal / g to 750 cal / g.
45. The method of claim 2, wherein the thermal decomposition onset of the hydrophobic organic material is 300°C or higher.
46. A method comprising subjecting the second silica-based aerogel composition of claim 1 to an elevated temperature, wherein the elevated temperature is at least 200°C.
47. A system comprising subjecting the second silica-based aerogel composition of claim 1 to an elevated temperature, wherein the elevated temperature is at least 200°C.
